Use of cyclic (-HIS-PRO) hydrates

By developing the polymorphic form of ring (-His-Pro) hydrate (Mode 2), the problem of unstable ring (-His-Pro) anhydrous form under high humidity conditions was solved, and higher stability and purity were achieved, which improved its application reliability as a drug.

CN119798264APending Publication Date: 2025-04-11NOVMETAPHARMA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893877.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-07-10
Filing Date
2019-06-21
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The anhydrous form of the ring (-His-Pro) is physically unstable under high humidity conditions and may have chemical instability, resulting in uncertainty in its application.

Method used

A new polymorphic form, namely ring (-His-Pro) hydrate (CHP hydrate or mode 2), was developed, obtained by using solvent crystallization separation methods, with stability better than amorphous ring (-His-Pro) or mode 1.

Benefits of technology

Mode 2 is more stable under typical room temperature storage conditions, can be used independently as a single component drug, with a purity of at least 90% or higher, significantly improving the stability and application reliability of the ring (-His-Pro).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798264A_ABST
    Figure CN119798264A_ABST
Patent Text Reader

Abstract

The invention relates to application of a novel polymorphic form of cyclo (-His-Pro) ('CHP'), in particular to application of cyclo (-His-Pro) hydrate in treatment of acute kidney injury, chronic kidney disease or renal fibrosis. An X-ray powder diffraction (XRPD) diffraction pattern of the hydrate provided by the invention comprises peaks with 2 theta being 10 + / -0.2 degrees, 13.7 + / -0.2 degrees, 17 + / -0.2 degrees, 18.1 + / -0.2 degrees and 27.3 + / -0.2 degrees; the initial endotherm of differential scanning calorimetry (DSC) is from 75 DEG C to 100 DEG C; the DSC initial heat release is 115 DEG C to 120 DEG C; a DSC thermogram has two endothermic peaks of which the maximum peak values are 100 DEG C and 170 DEG C; the chemical structure of the ring (-His-Pro) hydrate is shown in the specification. The hydrate can be used for treating acute kidney injury, chronic kidney diseases or renal fibrosis. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Related Applications

[0001] This application is filed on June 21, 2019, with application number 201980046575.8 and the name “ Ring (-HIS- PRO) " is a divisional application for a Chinese invention patent application. Technical Field

[0002] The present invention relates to novel polymorphic forms of cyclo(-His-Pro) ("CHP"). Background Art

[0003] Cyclic (-His-Pro), C 11 H 14 N 4 O 2 , known as an anhydrous dipeptide, CAS Registry Number 53109-32-3. It is an endogenous cyclic dipeptide derived from the in vivo hydrolytic removal of the amino-terminal pyroglutamic acid residue of hypothalamic thyrotropin-releasing hormone. Cyclic (-His-Pro) can be synthesized in vitro by conventional chemical methods. It is important in regulating the properties contributed by glial cells. Grotelli et al., Role of cyclo (His-Pro) in neurodegeneration, Int J Mol Sci. 2016. Aug;17(8):1332. Cyclic (His-Pro) is ubiquitous in the central nervous system and is a key substrate for organic cation transporters, which are strongly associated with neuroprotective effects. Cyclic dipeptides can also cross the brain-blood-barrier and, once in the brain, can affect different inflammatory and stress responses by modifying the Nrf2-NF-κB signaling axis.

[0004] The crystalline anhydrous form of cyclo(-His-Pro) ("anhydrous CHP" or "Mode 1") is the form reported in the literature to date and has potential therapeutic applications. However, certain anhydrous forms may be unstable. Potential disadvantages of using Mode 1 include: (1) significant physical instability in environments with high humidity; and (2) potential chemical instability due to water activity leading to the formation of diastereomers of the desired L,L-dipeptide, such as D,L-CHP, L,D-CHP or D,D-CHP. Therefore, there is a need in the art for more stable forms of CHP. Summary of the invention

[0005] The present invention provides a crystalline form of cyclo(-His-Pro) hydrate ("CHP hydrate" or "Pattern 2" compound) that can be characterized and distinguished from other solid forms of CHP using a variety of analytical techniques, including but not limited to X-ray powder diffraction (XRPD), solid state nuclear magnetic resonance (NMR or 13C SSNMR), Raman spectroscopy, differential scanning calorimetry (DSC), dynamic vapor sorption (DVS) and thermogravimetric analysis (TGA).

[0006] The applicant unexpectedly discovered that CHP hydrate (CAS RN: 2254826-95-2 (January 2019)) has better stability than the amorphous ring (-His-Pro) or Mode 1. Based on this surprising discovery, Mode 2 can be used alone as a single component drug, rather than using Mode 1 or a mixture of Mode 1 and Mode 2.

[0007] In one embodiment, the present invention is directed to a method for separation mode 2 by using solvent crystallization, rather than column chromatography currently used to separate anhydrous CHP.

[0008] In another embodiment, Pattern 2 is stable for about 6 months, or about 12 months, or about 18 months, or about 24 months, or about 36 months under typical room temperature storage conditions.

[0009] In yet another embodiment, the invention relates to substantially pure Mode 2 material. In some embodiments, the Mode 2 material is at least about 90% pure, or at least about 95%, 96%, 97%, 98%, 99%, or 100% pure.

[0010] In one embodiment, the purity of the sample is measured by any analytical method. In one embodiment, the purity is measured by high pressure liquid chromatography (HPLC), X-ray powder diffraction (XRPD), pKa analysis, polarized light microscopy (PLM), thermogravimetric analysis / differential thermal analysis (TG / DTA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), dynamic vapor sorption (DVS), variable temperature and humidity X-ray powder diffraction (VT- / VH-XRPD), 1 In another embodiment, the purity of the sample is measured by HPLC.

[0011] In one embodiment, the Mode 2 material is at least about 90% pure, or at least about 95%, 96%, 97%, 98%, 99%, or 100% pure as determined by HPLC.

[0012] In another embodiment, the Mode 2 material may have at least two of the following characteristics: (a) an X-ray powder diffraction pattern comprising at least two peaks selected from the group consisting of 10, 13.7, 17, 18.1, 20.2 and 27.3 degrees (2θ±0.2°); (b) a pKa of about 6.4; (c) birefringence with a fragmented rod-like morphology when analyzed by polarized light microscopy; (d) an initial weight loss of about 6.5% (0.9 equivalents of water), followed by degradation of the sample at about 280°C when analyzed by thermogravimetric analysis techniques; (e) In the first thermal cycle of DSC, the endotherm starts at about 99°C and peaks at about 102°C; (f) dehydrates beginning at less than about 10% relative humidity (RH), loses about 5.8 wt% from 10% to 0% RH (0.8 equivalents of water), and hydrates from 0% to about 40% RH in a 40° C. dynamic vapor sorption analysis; (g) dehydrates beginning at less than about 20% RH, loses about 6.1 wt % from about 20 to 0% RH (0.8 equivalents of water) in a 50° C. dynamic vapor sorption analysis, and rehydrates from 0 to about 40% RH; and (h) In a 60°C dynamic vapor sorption analysis, it begins to dehydrate below about 20% RH, loses about 7 wt% from about 20 to 0% RH (1.0 equivalent of water), and rehydrates from 0 to about 40% RH.

[0013] The present invention also provides a pharmaceutical composition comprising a mode 2 material and an excipient. This composition may include CHP hydrate from about 1% to about 50%, from about 5% to about 45%, from about 10% to about 40%, from about 15% to about 35%, from about 20% to about 30%, at least about 10%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, about 1%, about 2%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9% or about 10% (w / w). In one embodiment, the composition may include CHP hydrate from about 1% to about 10% (w / w). In a specific embodiment, the composition may include CHP hydrate about 4% (w / w).

[0014] In another embodiment, the composition can be prepared in the form of tablets, capsules, caplets, solution gels, trout, injectable sterile solutions, and the like.

[0015] Alternatively, the compositions taught herein can be formulated in powder form for reconstitution with a suitable carrier such as sterile pyrogen-free water before use. For example, a compound suitable for parenteral administration may include a sterile isotonic saline solution containing 0.1%-90% weight / volume of the compound. For example, the solution may contain about 5% to about 20%, more preferably about 5% to about 17%, more preferably about 8% to about 14%, and still more preferably about 10% of the compound.

[0016] Other embodiments of the compositions, methods, etc. of the present invention will be apparent from the following description, drawings, examples, and claims. It will be understood from the above and following description that each feature described herein and each combination of two or more such features are included within the scope of the present invention, as long as the features included in such combination are not mutually inconsistent. In addition, any feature or combination of features can be explicitly excluded from any embodiment or aspect. In the following description and claims, particularly when considered in conjunction with the accompanying examples and drawings, other aspects and embodiments are set forth. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The patent or application file contains at least one drawing executed in color. Copies of this patent or patent application publication with color drawing(s) will be provided by the Office upon request and payment of the necessary fee.

[0018] The foregoing features of the embodiments will be more readily understood by referring to the following detailed description and with reference to the accompanying drawings, in which:

[0019] Figure 1 is the X-ray powder diffraction pattern of crystalline mode 1.

[0020] Figure 2 is an XRPD comparison of (a) Mode 1 and (b) Mode 2 of CHP after dynamic vapor sorption (DVS). These results confirm that the prepared CHP material is Mode 2 (i.e., CHP hydrate) and that Mode 1 transforms to Mode 2 after DVS.

[0021] Figure 3 is a comparison of the X-ray powder diffraction patterns of mode 2 before and after DVS at 40% RH.

[0022] Figure 4 is an analysis of the X-ray powder diffraction pattern of Mode 2 after VT-DVS. It shows that the material is a mixture of Modes 1 and 2.

[0023] Figure 5 It is a comparison of X-ray powder diffraction patterns of about 30 mg of Mode 2 stored for seven days under three conditions: 40°C / 75% RH, 80°C and ambient light.

[0024] Figure 6 is an XRPD analysis of approximately 2.2 g of CHP hydrate (mode 2) weighed in a glass vial and placed in a vacuum oven set at 50°C for 1 hour.

[0025] Figure 7 is returned to the vacuum furnace for another 30 min for CHP hydrate or Mode 2 (blue line: Figure 5 In other words, Figure 7The purple line in is the XRPD analysis of the product of CHP hydrate (mode 2 material) after storage under vacuum at 50°C for 1.5 hours, showing mainly mode 2 mixed with some mode 1.

[0026] Figure 8 is the CHP hydrate returned to the oven or Mode 2 (blue line: from Figure 5 The temperature was raised to 80°C in the oven. The vial was placed in the oven for another 18 hours. In other words, Figure 8 The pink line in FIG. 5 is the XRPD analysis of the product of CHP hydrate (mode 2 material) after storage at 80° C. for 18 hours, showing mainly mode 1 mixed with some mode 2.

[0027] Fig. 9 is a comparison of the changes in mode 2 at different temperatures. Figure 5-7 The green line represents the pattern 2 sample stored at 50°C for 1 hour, the purple line represents the pattern 2 sample stored at 50°C for 90 minutes, and the pink line represents the pattern 2 sample (pink line) stored at 80°C for 18 hours.

[0028] Fig.10 An initial analysis of the resulting material (primarily Mode 1) is shown. The pKa value is 6.4.

[0029] Fig.11 Non-polarized microscopy analysis of the resulting CHP (mainly mode 1) is shown.

[0030] Fig.12 Polarized light microscopy analysis of the resulting CHP (mainly mode 1) is shown.

[0031] Fig.13 Mode 2 non-polarized microscopy and PLM analysis are shown.

[0032] Fig.14 Thermogravimetric analysis of the resulting CHP (mainly Mode 1) is shown.

[0033] Fig.15 Mode 2 thermogravimetric analysis / differential thermal analysis (TG / DTA) is shown.

[0034] Fig.16 The DSC analysis of the resulting CHP (mainly Mode 1) in the first thermal cycle is shown.

[0035] Fig.17 The DSC analysis of the resulting CHP (mainly mode 1) during the cooling cycle is shown.

[0036] Fig.18The DSC analysis of the resulting CHP (mainly Mode 1) in the second heating cycle is shown.

[0037] Fig.19 DSC analysis of mode 2 in the first heating cycle is shown.

[0038] Fig. 20 DSC analysis of mode 2 in the cooling cycle is shown.

[0039] Fig.21 DSC analysis of mode 2 in the second thermal cycle is shown.

[0040] Fig. 22 The FR-IR spectrum results of CHP hydrate are shown.

[0041] Fig.23 Results for the DVS isotherm plot for Mode 1 are shown, showing a 6.3% weight gain between 60% RH and 90% RH.

[0042] Fig.24 Isotherm results for DVS of Mode 1 are shown, followed by recrystallization showing slight hygroscopicity between 0-90% RH with a weight gain of 0.8% in the first heating cycle.

[0043] Fig.25 Results of the kinetic curves of Mode 1 DVS are shown.

[0044] Fig.26 XRPD of material before and after DVS is shown. Post-DVS XRPD analysis showed a new form, designated Mode 2.

[0045] Fig. 27 TG / DTA of CHP hydrate, mode 2, is shown.

[0046] Fig.28 is the isotherm plot of DVS, showing no change for CHP hydrate, Mode 2 material from 40% RH to 90% RH and from 10% RH to 90% RH.

[0047] Fig.29 The kinetic diagram of DVS of CHP hydrate, mode 2, is shown.

[0048] Fig.30 VT-DVS analysis of CHP hydrate, mode 2, after a single cycle at 40°C is shown, showing that the material begins to dehydrate below 10%, with a loss of 5.8% weight (equivalent to 0.8 moles of water). The material rehydrates at 0-40% RH.

[0049] Fig.31VT-DVS analysis of CHP hydrate, mode 2 after a single cycle at 50°C is shown, showing that the material begins to dehydrate below 20%, with a loss of 6.1% weight (equivalent to 0.8 moles of water). The material rehydrates at 0-40% RH.

[0050] Fig.32 VT-DVS analysis of CHP hydrate, mode 2, after a single cycle at 60°C is shown, showing that the material begins to dehydrate below 20%, with a loss of 7% weight (equivalent to 1.0 mole of water). The material rehydrates at 0-40% RH.

[0051] Fig.33 VT- / VH-XRPD analysis results of CHP hydrate, Mode 2 and Mode 1 are shown.

[0052] Fig.34 XRPD diffraction patterns of CHP hydrate, Mode 2 material, after various conditions of VT / DVS are shown. XRPD diffraction patterns of Mode 1 are provided for comparison.

[0053] Fig.35 shows that pattern 1 in DMSO-d 6 In 1 H-NMR spectrum.

[0054] Fig.36 shows that pattern 2 in DMSO-d 6 In 1 H-NMR spectrum.

[0055] Fig.37 The blue line and the red line are shown in Figure 1. 1 H-NMR spectra comparison.

[0056] Fig.38 The HSQC-NMR spectrum of mode 1 is shown.

[0057] Fig.39 The HSQC-NMR spectrum of a mixture of modes 1 and 2 is shown.

[0058] Fig.40 XRPD after initial freeze drying of Mode 1 is shown.

[0059] Fig.41 The XRPD of Pattern 1 after extended lyophilization (72 hours) is shown, from which the material recovered from freeze drying was found to be predominantly amorphous.

[0060] Fig.42 The XRPD of Mode 2 after initial lyophilization (72 hours drying) is shown, and the material returned from freeze drying was found to be Mode 2 after 72 hours of drying.

[0061] Fig.43 The approximate solubility of Mode 1 in various solvents is shown.

[0062] Fig.44 The solvent solubility results for Mode 1 based on the volume of solvent added are shown.

[0063] Fig.45 The polymorphs (pattern 1 or pattern 2) when pattern 1 is treated with various solvents are shown.

[0064] Fig.46 Primary polymorph screening solvents are shown.

[0065] Fig.47 XRPD diffraction patterns of polymorphs formed in various solvents - Fraction 1 are shown.

[0066] Fig.48 XRPD diffraction patterns of polymorphs formed in various solvents - Fraction 2 are shown.

[0067] Fig.49 XRPD diffraction patterns of polymorphs formed in various solvents - Fraction 3 are shown.

[0068] Fig.50 A primary polymorph screening temperature cycle is shown.

[0069] Fig.51 is an overlay of the XRPD diffraction patterns of mode 1 (blue) and mode 2 (red).

[0070] Fig.52 is a representative blank chromatogram.

[0071] Fig.53 It is a representative resolution solution chromatogram.

[0072] Fig.54 is a comparison of total impurities between CHP anhydrate (mode 1) and CHP hydrate (mode 2).

[0073] Fig.55 The LC-MS spectra of Mode 1 and Mode 2 confirmed the expected m / z of 235.1, corresponding to [C 11 H 14 N 4 O 2 ]H +Both modes give the same LC-MS as when dissolved in solvent (water) because there is no "solid form" or polymorph in solvent. LC-MS measures the soluble CHP, not the solid form.

[0074] Fig.56 The HPLC-UV chromatogram of the obtained CHP shows that the purity of the obtained CHP is 99.5%.

[0075] Fig.57 is the XRPD diffraction pattern of the solid recovered from the solvent solubility screen.

[0076] Figures 58-60 is the XRPD diffraction pattern of the solid recovered from the temperature cycle.

[0077] Fig.61 is the mode 2 XRPD diffraction pattern.

[0078] Fig.62 is the XRPD diffraction pattern obtained by repeated freeze-drying of CHP in water.

[0079] Fig.63 is the XRPD diffraction pattern obtained from the third freeze-drying attempt of CHP in water.

[0080] Figure 64-66 is the diffraction pattern associated with a temperature cycling experiment from a primary polymorph screening.

[0081] Fig.67 is the diffraction pattern associated with the evaporation experiment from the primary polymorph screening.

[0082] Fig.68 is the diffraction pattern associated with antisolvent addition from the primary polymorph screen.

[0083] Fig.69 is the XRPD result of mode 2 magnification.

[0084] Fig.70 is the XRPD diffraction pattern of the Mode 2 material obtained when the material was heated to 80°C.

[0085] Fig.71 is the XRPD diffractogram of the solid recovered by rapid rotary evaporation in the ethanol / DCM experiment.

[0086] Fig.72 is the XRPD diffraction pattern of the primary polymorph screening of Mode 2.

[0087] Fig.73 are images in mode 2 polarized and unpolarized light.

[0088] Fig.74This is a hot stage microscope image of CHP mode 2.

[0089] Fig.75 are polarized and non-polarized images of the material in the post-thermal stage.

[0090] Fig.76 This is Mode 2 TG / DTA-TG analysis.

[0091] Fig.77 This is the initial thermal cycle of DSC, which is considered to be an endotherm starting at 99°C and peaking at 102°C.

[0092] Fig.78 It is the cooling cycle of DSC.

[0093] Fig.79 This is the second heating cycle of DSC.

[0094] Fig.80 is the FT-IR spectrum of CHP mode 2.

[0095] Fig.81 is the diffraction pattern associated with VT- / VH-XRPD analysis.

[0096] Fig.82 is the DVS isotherm diagram of CHP mode 2.

[0097] Fig.83 is the DVS kinetic diagram of CHP mode 2.

[0098] Fig.84 Comparative XRPD diffractograms are shown.

[0099] Fig.85 is the DVS isotherm diagram of mode 2 at 40°C.

[0100] Fig.86 It is the kinetic diagram of mode 2 at 40°C.

[0101] Fig.87 is the isotherm diagram of mode 2 at 50°C.

[0102] Fig.88 It is the kinetic diagram of mode 2 at 40°C.

[0103] Fig.89 is the isotherm diagram of mode 2 at 60°C.

[0104] Fig.90 It is the kinetic diagram of mode 2 at 60°C.

[0105] Fig.91 Comparative XRPD diffractograms are shown.

[0106] Fig.92An image of the Mode 1 sample after dissolution is shown.

[0107] Fig.93 An image of the Mode 2 sample after dissolution is shown.

[0108] Fig.94 is the XRPD 2θ diffraction pattern of the sample tested under 40°C / 75% RH, 80°C and ambient light conditions.

[0109] Fig.95 This is one of the HPLC chromatograms of the stable sample. Stable for 1 week at 40°C / 75% RH.

[0110] Fig.96 This is one of the HPLC chromatograms of a stable sample. Stable for 1 week at 80°C.

[0111] Fig.97 This is one of the HPLC chromatograms of the stability sample. Stable for 1 week at ambient temperature.

[0112] Fig.98 is the XRPD 2θ diffraction pattern of pure mode 1 at two weeks time point.

[0113] Fig.99 is the XRPD 2θ diffraction pattern of Mode 2 at two weeks time point.

[0114] Fig.100 is the XRPD 2θ diffraction pattern of pure mode 1 at four weeks.

[0115] Fig.101 is the XRPD 2θ diffraction pattern of Mode 2 at four weeks.

[0116] Fig.102 is the XRPD 2θ diffraction pattern of pure mode 1 at eight weeks.

[0117] Fig.103 is the XRPD 2θ diffraction pattern of Mode 2 at eight weeks.

[0118] Fig.104 is the HPLC chromatogram of pure mode 1-starting time point.

[0119] Fig.105 It is the HPLC chromatogram of pure mode 1-2 weeks.

[0120] Fig.106 It is the HPLC chromatogram of pure mode 1-4 weeks.

[0121] Fig.107 It is the HPLC chromatogram of pure mode 1-eight weeks.

[0122] Fig.108 is the HPLC chromatogram of pure mode 2-starting time point.

[0123] Fig.109 is the HPLC chromatogram of Mode 2-two weeks.

[0124] Fig.110 It is the HPLC chromatogram of mode 2-four weeks.

[0125] Fig.111 are XRPD results from storage at 40°C / 75% RH.

[0126] Fig.112 Representative overlaid chromatograms of blank, resolution solution, and sample solution (6M) for impurity testing.

[0127] Fig.113 It is the primary polymorph screen evaporations.

[0128] Fig.114 It is a summary table of primary polymorph screening.

[0129] Fig.115 This is a summary of the 8-week stability appearance results. DETAILED DESCRIPTION

[0130] Various aspects and embodiments will be fully described herein. However, these aspects and embodiments may be embodied in many different forms and should not be construed as limiting; rather, these embodiments are provided to make the present invention exhaustive and complete and will fully convey the scope of the subject matter of the present invention to those skilled in the art. All publications, patents, and patent applications cited herein, whether supra or infra, are incorporated herein by reference in their entirety. A. Definition

[0131] Unless otherwise defined, all terms and phrases used herein include the meanings that the terms and phrases have acquired in the art unless expressly stated to the contrary or obvious from the context in which the term or phrase is used. Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present invention, specific methods and materials are now described.

[0132] Unless otherwise stated, the use of single numerical values ​​is stated as approximate values, as if there is a word "about" or "approximately" before these values. Similarly, unless otherwise explicitly stated, the values ​​in the various ranges specified in this application are stated as approximate values, as if both the minimum and maximum values ​​in the stated ranges are preceded by the words "about" or "approximately". In this way, changes above and below the stated ranges can be used to obtain results substantially the same as the values ​​in the stated ranges. As used herein, the terms "about" and "approximately" should have clear and common meanings when referring to numerical values ​​for those of ordinary skill in the art most closely associated with the disclosed subject matter or for those of ordinary skill in the field associated with the range or element in question. The amount of widening from the strict numerical boundaries depends on many factors. For example, some factors that can be considered include the criticality of the element and / or the impact of a given amount of variation on the performance of the claimed subject matter, as well as other considerations known to those skilled in the art. As used herein, the use of different amounts of significant figures for different numerical values ​​does not mean limiting how the use of the words "about" or "approximately" will be used to expand a specific numerical value or range. Therefore, generally, "about" or "approximately" expands the numerical value. In addition, the disclosed ranges are intended as a continuous range including every value between the minimum and maximum values ​​plus the broadening of the range provided by the use of the term "about" or "approximately." Therefore, recitation of ranges of values ​​herein are merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, and each separate value is incorporated into the specification as if it were individually recited herein.

[0133] The terms "parenteral administration" and "administered parenterally" are art-recognized and refer to modes of administration other than enteral and topical administration, usually by injection, and include, but are not limited to, intravenous, intramuscular, intraarterial, intrathecal, intracapsular, intraorbital, intracardiac, intradermal, intraperitoneal, transtracheal, subcutaneous, subcutaneous, intraarticular, subcapsular, subarachnoid, intraspinal, and intrasternal injection.

[0134] As used herein, the term "active agent" or "drug" refers to any chemical substance that causes a biochemical reaction when administered to a human or animal. The drug can act as a substrate or product of a biochemical reaction, or the drug can interact with a cell receptor and cause a physiological response, or the drug can bind to a receptor and block the receptor to cause a physiological response.

[0135] As used herein, the term "bioequivalent" refers to two compositions, products, or methods where the AUC, partial AUC, and / or C max The 90% confidence interval (CI) was between 0.80 and 1.25.

[0136] The term "CHP hydrate" (a / k / a "Pattern 2") refers to the compound identified by CAS Registry Number: 2254826-95-2 issued on January 7, 2019.

[0137] The phrase "substantially pure" means that a substance has an overall purity of greater than 90%, or greater than 95%, or greater than 96%, or greater than 97%, or greater than 98%, or greater than 99%, or greater than 99.5%. For example, the phrase "substantially pure substance A" means that the purity of substance A is at least 90% relative to all impurities, or the purity of substance A is at least 95% relative to all impurities, or the purity of substance A is at least 98% relative to all impurities, or the purity of substance A is at least 99% relative to all impurities.

[0138] In one embodiment, the purity of the sample is measured by any analytical method. In one embodiment, the purity is measured by HPLC, X-ray powder diffraction (XRPD), pKa analysis, polarized light microscopy (PLM), thermogravimetric analysis / differential thermal analysis (TG / DTA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), dynamic vapor sorption (DVS), variable temperature and humidity X-ray powder diffraction (VT- / VH-XRPD), 1 H nuclear magnetic resonance (NMR) and / or heteronuclear single quantum coherence (HSQC) NMR.

[0139] In some embodiments, the term "substantially as shown by..." when referring to an X-ray powder diffraction pattern or a differential scanning calorimetry pattern means that the pattern is not necessarily the same as those described herein, but is within the limits of experimental error or deviation when considered by one of ordinary skill in the art.

[0140] The term "therapeutically effective amount" refers to an amount sufficient to effect treatment when administered to a human in need of such treatment, as defined below. The therapeutically effective amount will vary depending on the human subject being treated, the weight and age of the human subject, the severity of the disease condition, the mode of administration, etc., and can be readily determined by one of ordinary skill in the art. B. Introduction

[0141] The present invention relates to a new compound CHP hydrate, its use and its preparation. The description is as follows:

[0142] On January 7, 2019, CHP hydrate was assigned CAS Registry Number (CAS RN): 2254826-95-2, with CA Index Name: Pyrrolo[1,2-a]pyrazine-1,4-dione,hexahydro-3-(1H-imidazol-5-ylmethyl)-,hydrate(1:1),(3S,8aS)-. The molecular weight of CHP hydrate is 252.3 g / mol.

[0143] Those skilled in the art will appreciate that other commonly recognized nomenclature systems and symbols may be used to name or identify compound structures. For example, compounds may be named or identified by common names, systematic or non-systematic names. Nomenclature systems and symbols generally recognized in the chemical field include, but are not limited to, Chemical Abstracts Service (CAS) and International Union of Pure and Applied Chemistry (IUPAC). Therefore, according to CAS, the compound structures provided above identified as pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(1H-imidazole-5-ylmethyl)-, hydrate (1:1), (3S,8aS)- may be identified by other nomenclature equivalent to the CAS nomenclature. C. General Characterization of CHP Hydrate

[0144] In one embodiment, CHP hydrate has an X-ray powder diffraction pattern (XRPD) including characteristic peaks at about 13.7 degrees, 17 degrees, and about 27.3 degrees 2θ. In some embodiments, the X-ray powder diffraction pattern further includes any one or more of characteristic peaks at about 10 degrees, about 13.7 degrees, about 17 degrees, about 18.1 degrees, and 24.5 degrees 2θ.

[0145] In some embodiments, the CHP hydrate has a melting temperature of about 170° C. to about 172° C. In one variation, the CHP hydrate has an X-ray powder diffraction pattern including any one or more of characteristic peaks at about 10 degrees, about 13.7 degrees, about 17 degrees, about 18.1 degrees, about 20.2 degrees, and about 27.3 degrees 2θ.

[0146] It should be understood that relative XRPD intensities may vary depending on many factors, including sample preparation, mounting, and the instrumental and analytical procedures and settings used to obtain the spectra.Accordingly, the peak conventions 2θ listed herein include variations of ±0.2 degrees.

[0147] In other embodiments, the CHP hydrate is characterized as having an onset melting temperature as measured by differential scanning calorimetry at about 170° C. In other embodiments, the CHP hydrate is substantially free of solvent.

[0148] In some embodiments of CHP hydrate, at least one, at least two, at least three, at least four, or all of the following (a)-(f) apply: (a) the CHP hydrate is substantially free of solvent; (b) the CHP hydrate is crystalline; (c) the CHP hydrate has substantially Figure 2 (b) X-ray powder diffraction pattern shown; (d) CHP hydrate has substantially Figure 19-21 The differential scanning calorimetry thermogram is shown; (e) CHP hydrate has an onset melting temperature of about 170° C. as measured by differential scanning calorimetry; and (f) CHP hydrate is stable under room temperature storage conditions.

[0149] In some embodiments, the CHP hydrate comprises at least one, at least two, or all of the following properties: (a) Basically Figure 2 (b) X-ray powder diffraction pattern shown; (b) Basically Figure 19-21 Differential Scanning Calorimetry thermogram shown; as well as (c) The onset melting temperature measured by differential scanning calorimetry is about 170°C.

[0150] In some embodiments, CHP hydrate has an X-ray powder diffraction pattern showing at least two maximum peaks, substantially as Figure 2 (b) The X-ray powder diffraction pattern shown in FIG. In some embodiments, the CHP hydrate has an X-ray powder diffraction pattern showing at least three maximum peaks, substantially as shown in FIG. Figure 2 (b) The X-ray powder diffraction pattern shown in FIG. In some embodiments, the CHP hydrate has an X-ray powder diffraction pattern showing at least four maximum peaks, substantially as shown in FIG. Figure 2 (b) The X-ray powder diffraction pattern shown in FIG. In some embodiments, the CHP hydrate has an X-ray powder diffraction pattern showing at least five maximum peaks, substantially as shown in FIG. Figure 2 (b) The X-ray powder diffraction pattern shown in. In some embodiments, the CHP hydrate has an X-ray powder diffraction pattern showing at least six maximum peaks, substantially as shown in Figure 2 (b) shows the X-ray powder diffraction pattern. D. Pharmaceutical Composition

[0151] In one embodiment, a pharmaceutical composition comprising a substantially pure Mode 2 compound and a pharmaceutically acceptable carrier is provided. For example, the pharmaceutical composition can contain from about 1% to about 20% (wt%) (i.e., about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%) of the substantially pure Mode 2 compound, which accounts for about 1% to about 20% (wt%) of the total pharmaceutical composition. As a further example, the pharmaceutical composition may include about 1% to about 100%, about 1% to about 10%, about 10% to about 20%, about 20% to about 30%, about 30% to about 40%, about 40% to about 50%, about 50% to about 60%, about 60% to about 70%, about 70% to about 80%, about 80% to about 90%, about 90% to about 100% (wt%) of the Mode 2 compound of the total pharmaceutical composition. For example, the pharmaceutical composition may include about 1% to about 40% (wt%) of the Mode 2 compound of the total pharmaceutical composition. In a specific embodiment, the pharmaceutical composition may include about 4% (wt%) of the Mode 2 compound of the total pharmaceutical composition.

[0152] In another embodiment, a pharmaceutical composition comprising a substantially pure Pattern 2 compound, another therapeutically active agent, and a pharmaceutically acceptable carrier is provided. In one embodiment, the active agent is selected from a biomolecule, a bioactive agent, a small molecule, a drug, a prodrug, a drug derivative, a protein, a peptide, a vaccine, an adjuvant, an imaging agent (e.g., a fluorescent moiety), a polynucleotide, or a metal. In another embodiment, the active agent is zinc.

[0153] In one embodiment, a Mode 2 drug substance meets the requirements of ICH purity guideline Q.2A regarding the level of impurities in CHP.

[0154] In another embodiment, the compositions of the present invention can be administered in a variety of ways, including orally, topically, parenterally, intravenously, intradermally, colonically, rectally, intramuscularly, or intraperitoneally.

[0155] Compositions can be formulated for parenteral administration by injection, for example, by push injection (drug substance) or continuous infusion (continuous infusion). Injectable preparations can be added with optional preservatives in unit dosage form (unit dosage form) in ampoules or multi-dose containers. Parenteral preparations can be packaged in ampoules, disposable syringes or multi-dose vials made of glass, plastics, etc. Preparations can take the form of suspensions, solutions or emulsions such as in oily or aqueous vehicles, and can contain agents such as suspending agents, stabilizers and / or dispersants.

[0156] For example, the parenteral preparation may be a sterile injectable solution or suspension in a non-toxic parenterally acceptable diluent or solvent. Among the acceptable carriers and solvents, water, 0.9% saline solution or other suitable aqueous media may be used.

[0157] In one embodiment, the concentration of the intravenous "solution" preparation is about 1 mg / liter to about 200 mg / ml, about 5 mg / ml to about 150 mg / ml, about 10 mg / ml to about 100 mg / ml. In another embodiment, the concentration of the intravenous "solution" preparation is about 1 mg / liter, about 2 mg / liter, about 3 mg / liter, about 4 mg / liter, about 5 mg / liter, about 6 mg / liter, about 7 mg / liter, about 8 mg / liter, about 9 mg / liter, about 10 mg / liter, about 11 mg / liter, about 12 mg / liter, about 13 mg / liter, about 14 mg / liter, about 15 mg / liter, about 20 mg / liter, about 25 mg / liter, about 30 mg / liter, about 35 mg / liter, about 40 mg / liter, about 45 mg / liter, about 50 mg / liter, about 55 mg / liter. g / liter, about 60mg / liter, about 65mg / liter, about 70mg / liter, about 75mg / liter, about 80mg / liter, about 85mg / liter, about 90mg / liter, about 95mg / liter, about 100mg / liter, about 110mg / liter, about 120mg / liter, about 130mg / liter, about 140mg / liter, about 120mg / liter, about 130mg / liter, about 140mg / liter, about 150mg / liter, about 160mg / liter, about 170mg / liter, about 180mg / liter, about 190mg / liter, about 200mg / liter.

[0158] In another embodiment, the composition may be formulated as a diffusive (slow drip) formulation or an intravenous bolus injection.

[0159] In another embodiment, the Pattern 2 compound can be administered orally or formulated for oral administration. Administration can be by rapid release tablets and capsules or enteric coated tablets, etc. In preparing a pharmaceutical composition comprising at least one compound described herein, the active ingredient is typically diluted with an excipient and / or encapsulated in a carrier that can be in the form of a capsule, pouch, paper or other container. When an excipient is used as a diluent, it can be in the form of a solid, semisolid or liquid substance that serves as a vehicle, carrier or medium for the active ingredient. Thus, the composition can be in the form of tablets, pills, powders, lozenges, sachets, cachets, elixirs, suspensions, emulsions, solutions, syrups, aerosols (as solids or in liquid media), ointments, soft and hard gelatin capsules, sterile injectable solutions and sterile packaged powders.

[0160] Some examples of suitable excipients include lactose, glucose, sucrose, sorbitol, mannitol, starch, gum arabic, calcium phosphate, alginates, tragacanth, gelatin, calcium silicate, microcrystalline cellulose, hydroxypropylcellulose, polyvinylpyrrolidone, cellulose, USP or sterile water, syrup base and methylcellulose. The formulation may additionally include: lubricants such as talc, magnesium stearate and stearic acid; wetting agents; emulsifiers and suspending agents; preservatives such as methyl and propylhydroxy-benzonates; sweeteners; and flavoring agents.

[0161] In some embodiments, the composition is formulated in unit dosage form. The term "unit dosage form" refers to physically discrete units suitable as unit doses for human subjects and other mammals, each unit containing a predetermined amount of active substance (therapeutically effective amount) calculated to produce the desired therapeutic effect, associated with a suitable pharmaceutical excipient (e.g., tablet, capsule, ampoule). The compound is usually administered in a pharmaceutically effective amount. In some embodiments, each dosage unit contains about 1 mg to about 100 mg of mode 2 compound. In some embodiments, each dosage unit contains about 2 mg to about 60 mg, about 3 mg to about 50 mg, about 4 mg to about 40 mg, about 5 mg to about 30 mg, about 6 mg to about 20 mg, about 8 mg to about 15 mg, or about 8 mg to about 10 mg of mode 2 compound.

[0162] In other embodiments, each dosage unit contains about 1 mg, about 2 mg, about 3 mg, about 4 mg, about 5 mg, about 6 mg, 7 mg, about 8 mg, about 9 mg, about 10 mg, about 11 mg, about 12 mg, about 13 mg, about 14 mg, about 15 mg, about 16 mg, about 17 mg, about 18 mg, about 19 mg, about 20 mg, about 30 mg, about 40 mg, about 50 mg, about 60 mg, about 70 mg, about 80 mg, about 90 mg or about 100 mg of Pattern 2 compound.

[0163] In one embodiment, the subject receives one or more dosage units per day. In another embodiment, the subject receives 15 mg of Pattern 2 compound per day.

[0164] To prepare solid compositions such as tablets, the active principle ingredient is mixed with a pharmaceutical excipient to form a solid mixed-blend composition containing a homogeneous mixture of the compound of the invention. When referring to these mixed-blends as homogeneous, it is meant that the active ingredient is evenly dispersed throughout the composition so that the composition can be readily subdivided into equally effective unit dosage forms, such as tablets, pills, and capsules.

[0165] Tablet of the present invention or pill can be powder coating or otherwise compound, to provide the advantage of prolonged effect or protection of the dosage form that is not affected by the acidic conditions of the stomach.For example, tablet or pill can comprise inner dosage and outer dosage component, and the latter is the coating form on the former.These two components can be separated by enteric layer, and this enteric layer is used to resist the decomposition in the stomach and allows the inner component to enter the duodenum intact or be delayed release.Multiple materials can be used for this enteric layer or coating, and this material comprises the mixture of multiple polymeric acid and polymeric acid and the material such as shellac, spermol and cellulose acetate.In one embodiment, film coating is the coating based on polyvinyl alcohol.

[0166] Compounds useful in the compositions and methods include those described herein in any pharmaceutically acceptable form thereof, including isomers such as diastereomers and enantiomers, salts, solvates and polymorphs, as well as racemic mixtures and pure isomers of the compounds as applicable herein.

[0167] Suitable excipients include binders, fillers, disintegrants, lubricants, antioxidants, chelating agents and colorants.

[0168] Table 1 provides an exemplary formulation for oral dosage form, comprising (based on weight % of the ingredients): Table 1: Exemplary formulations for oral dosage forms include (based on weight % of the ingredients) Element 1 2 3 4 5 6 7 8 9 10 CHP Hydrate 85 70 60 50 40 30 20 10 5 2 Binder 9 10 20 30 30 40 40 40 40 40 Disintegrants 5 5 5 5 5 5 5 5 5 5 Lubricants 1 1 1 1 1 1 1 1 1 1 filler 0 14 14 14 24 24 34 44 49 52 E. Preparation of CHP Hydrate

[0169] In some embodiments, CHP hydrate is obtained by crystallization. CHP anhydrate is dissolved in 2-2.5v of EtOH / water or acetone / water at 50°C, and the system is then cooled to 35°C. Next, 0.5v of methyl tert-butyl ether (MtBE) is added, followed by 0.5% seed (CHP hydrate). After stirring for 2 hours, the system is cooled to 5°C within 2 hours. Finally, 7v of MtBE is added within 8 hours, followed by stirring for 8 hours.

[0170] Solubility evaluation of a batch of CHP Mode 1 showed high solubility in all aqueous solvent mixtures except the ethanol:water:MtBE mixture with the highest percentage of MtBE. Particularly high solubility was observed in water and water:acetone mixtures. The material was poorly soluble in acetone, acetonitrile and THF (≤10 mg / mL). Two-point solubility experiments showed that of the two solvent systems evaluated (ethanol:water:MtBE and acetone:water), ethanol:water:MtBE allowed slightly higher yields but at the risk of forming Mode 1, while acetone:water allowed exclusivity of Mode 2 but at the risk of reduced yield.

[0171] Two sets of small-scale crystallization trials (500 mg scale) were performed using CHP Mode 1, the first using an acetone:water solvent system and the second using an ethanol:water:MtBE solvent system. Antisolvent was added at either 5°C or 50°C. Mode 2 was recovered exclusively by XRPD regardless of the solvent system or antisolvent addition temperature. Ethanol:water / MtBE produced larger particles, especially when the solid was isolated at higher temperature (50°C). Solvent losses due to evaporation (especially in ethanol:water:MtBE) resulted in much lower calculated yields compared to the mass of solid recovered after filtration.

[0172] These crystallization development studies explored combinations of cooling and antisolvent addition protocols with the goal of obtaining good yields and particle uniformity. These studies showed that at 20 g scale, using 2% ground seed addition, stepwise addition of antisolvent, holding at 29° C. for eight hours, followed by cooling to 5° C., proved to be the most promising protocol with respect to particle uniformity (evaluated by optical microscopy and FBRM) and yield. X-ray powder diffraction (XRPD)

[0173] In one embodiment, the present invention relates to a substantially pure cyclic (-His-Pro) hydrate (Pattern 2) compound as follows: Characterized in that the XRPD diffraction pattern comprises peaks at about 17 degrees (± 0.2°) and about 27.3 degrees (± 0.2°) 2θ.

[0174] One embodiment of substantially pure Mode 2 is characterized by an X-ray powder diffraction pattern comprising at least three peaks selected from the group consisting of 13.7, 17, 18.1, 20.2, and 27.3 degrees (± 0.2°) 2θ. Another embodiment is characterized by an XRPD diffraction pattern comprising at least two peaks selected from the group consisting of 10, 13.7, 17, 18.1, 20.2, and 27.3 degrees (± 0.2°) 2θ. G. Nuclear Magnetic Resonance (NMR) or 13 CSSNMR

[0175] In one embodiment, Mode 2 1 The H NMR spectrum showed the following chemical shifts: 1 H NMR (400 MHz, D 2 O) δ7.58 (d, 1H, J = 3.2Hz), 6.82 (d, 1H, J = 3.2Hz), 4.42 (m, 1H), 4.12 (m, 1H), 3.36-3 .47 (m, 2H), 3.05-3.09 (m, 2H), 2.12 (br, 1H), 1.80-1.84 (m, 2H), 1.37-1.40 (m, 1H).

[0176] In one embodiment, the CHP hydrate of the present invention exhibits the same activity as CHP-anhydrate in DMSO-d 6 Solvents are essentially the same 1 H-NMR. This included the following values: 1.7 ppm (m, 3H), 2.1 ppm (m, 1H), 2.5 ppm (s, 3H), 3.2 ppm (d, 1H), 3.5 ppm (m, 1H), 4.2 ppm (m, 2H), 7.0 ppm (s, 1H), 7.6 ppm (s, 1H), 8.1 ppm (s, 1H). H. Solid-state infrared spectrometer

[0177] In one embodiment, the solid infrared spectrum of Mode 2 shows 3457, 3411 (m); 3292, 3211 (m); 2976, 1658, 1633 (m); and 1445-1424 (m) cm -1 signal. I. Differential Scanning Calorimetry (DSC)

[0178] In another embodiment, the onset endotherm of Mode 2 is found to be about 100±2°C and 171±2°C. In other embodiments, Mode 2 (CHP hydrate) of the present invention exhibits an onset endotherm at about 75°C to about 100°C. J. Dynamic evaporative adsorption (DVS)

[0179] In yet another embodiment, the Mode 2 dynamic vapor sorption exhibits one or more of the following: - dehydrated below 10% RH with a loss of 6 ± 0.2 wt % and rehydrated from 0% to 40% RH at 40°C; - dehydrates below 20% RH with a loss of 6±0.2 wt % and rehydrates from 0% to 40% RH at 50°C; and - Dehydrated below 20% RH with a loss of 7 ± 0.2 wt % and rehydrated at 60°C from 0% to 40% RH.

[0180] In other embodiments, the CHP hydrate of the present invention exhibits a weight loss of about 3% to about 9%, or about 4% to about 8.5%, or about 5% to about 8%. In another embodiment, the CHP hydrate of the present invention exhibits a weight loss of about 5.5% to about 7.3%.

[0181] In yet another embodiment, the CHP hydrate of the present invention exhibits a weight loss of about 5.8% to about 7.0%. K. Thermogravimetric analysis (TGA)

[0182] In another embodiment, the Mode 2 TGA shows a 6 ± 0.5% weight loss before degradation.

[0183] In other embodiments, the CHP hydrate of the present invention exhibits at least one endothermic phenomenon at about 75-85° C., i.e., loss of water. In another embodiment, the CHP hydrate of the present invention exhibits at least one exothermic phenomenon at about 115 to about 120° C., i.e., recrystallization into Mode 1. L. Melting temperature

[0184] In another embodiment, the melting temperature of Mode 2 is 170±2°C. M. Metastable Zone Width (MSZW) Measurement

[0185] In another embodiment, the absence of precipitation at 0% MtBE indicates that the addition of an antisolvent is required for crystallization to occur. At 10% MtBE, a metastable zone width of approximately 43.2°C was observed. At 20% MtBE, CHP remained in solution until the starting concentration was >100 mg / mL. The metastable zone widths for the 325 and 425 mg / mL experiments were determined to be approximately 35.2 and approximately 30.7°C, respectively. Increasing the MtBE content to 30% v / v resulted in an MSZW of approximately 30±0.5°C (at 325 mg / mL). In addition, at 60% MtBE, the MSZW was 51.4°C (at 100 mg / mL). At 80% MtBE, samples prepared at concentrations of 100 mg / mL and 425 mg / mL remained as slurries throughout the experiment, even at higher temperatures. Throughout the metastable zone width analysis, a trend was noted that temperatures of approximately 56-61°C were required to obtain clear points. P. Treatment methods

[0186] The Pattern 2 compounds of the present invention can be used in therapeutically effective amounts to treat a variety of diseases and conditions, such as diabetes and other metabolic diseases, neurodegenerative diseases, Alzheimer's disease, Parkinson's disease, Huntington's disease, acute kidney injury (AKI), chronic kidney disease (CKD), renal fibrosis, to provide cellular protection against oxidative damage, to inhibit inflammatory responses in PC12 cell lines, and as appetite suppressants. Example

[0187] The following examples are used to illustrate certain embodiments of the present invention. However, those skilled in the art will appreciate that, without departing from the spirit and scope of the present invention, the disclosed specific embodiments may be modified and still obtain the same or similar results. Therefore, all of the contents set forth herein should be interpreted as illustrative rather than restrictive. Example 1 - Transition from Mode 1 (anhydrous CHP) to Mode 2 (CHP hydrate)

[0188] 2 g of mode 1 material (batch number PS00726-55-D) was dissolved in 1 mL of water at 80°C, and 1 mL of water was added to offset the large amount of evaporation. At 80°C, a clear dark brown solution was obtained. Next, the solution was quickly cooled to 50°C, and 9.5 volumes (19 mL) of acetone were added to the solution to obtain a light yellow solution. No oiling or precipitation was detected. The solution was cooled to room temperature, causing a large amount of solid precipitation. The solution was cooled to 6°C (to increase the yield), and the slurry was filtered. The solid was dried on the filter to prevent dehydration. Because it is dehydrated to mode 1 at 80°C or higher under vacuum, vacuum drying at 50°C is considered safe for preserving mode 2. XRPD confirmed that the product is mode 2 with a yield of about 72%.

[0189] A batch of CHP hydrate was analyzed by various techniques including: X-ray powder diffraction (XRPD), pKa analysis, polarized light microscopy (PLM), thermogravimetric analysis / differential thermal analysis (TG / DTA), differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FT-IR), dynamic vapor sorption (DVS), variable temperature and humidity X-ray powder diffraction (VT- / VH-XRPD), 1 H nuclear magnetic resonance (NMR) and heteronuclear single quantum coherence (HSQC) NMR. AX-ray powder diffraction (XRPD)

[0190] XRPD analysis was performed on a PANalytical X'pert pro, scanning the samples between 3 and 35° 2θ. The material was lightly ground to loosen any agglomerates and loaded onto a porous plate with a Kapton or Mylar polymer film to support the sample. The porous plate was then placed in the diffractometer and the Cu K radiation source (α1 The analysis was performed in transmission mode (with a step size 2θ of 0.0130°) using a 40 kV / 40 mA generator setup.

[0191] like Figure 1 As shown, this batch was crystallized by XRPD and designated as Mode 1. A 5 g sample of CHP hydrate was subjected to XRPD analysis. The sample was weighed in a glass vial and 6 mL of a 90:10 ethanol / water mixture was added to prepare a slurry. The mixture was then stirred at ambient temperature for about 24 hours before analysis by XRPD. Figure 2 As shown, it is confirmed that the material is Mode 2 ( Figure 2 (b)). Figure 3 As shown, the analysis of Mode 2 after DVS showed no change in form after DVS at 40% RH. Figure 4 As shown, the analysis of Mode 2 shows that after various temperature DVS (VT-DVS), the material is a mixture of Modes 1 and 2. Figure 5 As shown, approximately 30 mg of Mode 2 (black line, Figure 5 ) were stored for seven days under three conditions: 40°C / 75% RH, 80°C, ambient light. XPRD analysis was performed to evaluate any changes in material form. After seven days, the samples stored at 40°C / 75% RH (blue line, Figure 5 ) and samples stored under ambient light (green line, Figure 5 The samples stored at 80°C transformed to Mode 1 (red line, Figure 5 ).like Figure 7 As shown, the mode 2 sample ( Figure 7 The blue line) was returned to the vacuum oven and kept for another 30 minutes. XRPD analysis ( Figure 7 The purple line) shows that the material is still mostly Mode 2 with some Mode 1 peaks.

[0192] like Figure 6 As shown, CHP hydrate (mode 2) was weighed in a glass vial and placed in a vacuum oven set at 50°C for 1 hour. XRPD analysis (green line) showed that the material was still predominantly mode 2 with some mode 1 peaks.

[0193] like Figure 8 As shown, it will come from Figure 5The input material (black line) was returned to the oven where the temperature was raised to 80°C. The vial was left in the oven for an additional 18 hours. XRPD analysis (pink line) showed that the material was a mixture of Modes 1 and 2. There was an additional peak at 8° 2θ that was not seen in any of the previous modes. Fig. 9 As shown, Figure 5 The pattern 2 was dried at three different time periods and the results were analyzed by XRPD. The sample dried at 50°C for 1 hour produced a pattern 2 with a peak of pattern 1 (green line), the sample dried at 50°C for 90 minutes also produced a pattern 2 with a peak of pattern 1 (purple line), and the sample dried at 80°C for 18 hours showed a mixture of pattern 1 and pattern 2 (pink line).

[0194] Fig.34 The different conditions for the transition from Mode 2 to Mode 1 are summarized. The samples in Mode 2 (black line, Fig.34 ) transforms mode 2 to mode 1 within 20 minutes (run 3, blue line), while it remains in mode 2 even after 1 hour at 0% RH and ambient temperature (red line). Mode 2 is stable at 40% RH and ambient temperature (run 1, brown line). B. pKa analysis

[0195] The pKa analysis for Mode 1 was performed by a potentiometric technique, which is an acid / base titration to determine the pKa point.

[0196] like Fig.10 As shown, the result of the analysis of anhydrous CHP (mode 1) is a pKa value of 6.4. C. Optical Microscopy (Non-Polarized) and Polarized Light Microscopy (PLM)

[0197] Visual measurements were performed using an optical microscope with a calibrated Linkam THM600 heat stage, with a connected controller unit coupled to an Olympus BX50 polarizing microscope equipped with a Motic camera and image capture software (Motic Images Plus 2.0). Approximately 0.5 mg of material was placed on a microscope cover slip and heated at a rate of 10°C / min, with images taken at regular intervals to record any thermal transitions. Unless otherwise stated, all images were recorded using a 10x objective.

[0198] (PLM) analysis was performed using an Olympus BX50 polarizing microscope equipped with a Motic camera and image capture software (Motic Image Plus 2.0). Unless otherwise stated, all images were recorded using a 20x objective. The degree of crystallinity (birefringence) was determined by PLM. Polarized light microscopy is designed to observe and photograph visible samples, primarily due to the optical anisotropy of the sample.

[0199] Fig.11 (non-polarized light microscopy) and 12 (polarized light microscopy) demonstrated that the CHP provided (mainly mode 1) was birefringent and had no clear morphology. Fig.13 As shown, Mode 2 was found to be birefringent with a fragmented, rod-like morphology. In other embodiments, the CHP hydrate of the present invention (Mode 2) exhibited a fragmented, rod-like morphology under PLM. D. Thermogravimetric analysis / differential thermal analysis (TG / DTA)

[0200] Approximately 5 mg of material was weighed into an open aluminum pan and loaded into a Seiko 6200 / 7200 simultaneous thermogravimetric / differential thermal analyzer (TG / DTA) and kept at room temperature. The sample was then heated from 20°C to 300°C at a rate of 10°C / min, during which the change in sample weight and any differential thermal phenomena (DTA) were recorded. Nitrogen was used as a purge gas at a flow rate of 300 cm 3 / min.

[0201] like Fig.14 As shown, TGA analysis of Mode 1 shows an initial weight loss of 0.6% (0.08 equivalents of water) at about 75-85°C. This 0.6% of water belongs to surface water - unbound water. Two additional weight losses of 0.2% and 0.3% (0.03 and 0.04 equivalents of water, respectively) were observed before the sample degraded at about 260°C. The first weight loss may be due to the loss of water from a small amount of Mode 2 material mixed in the material to form Mode 1. Based on the weight loss, the amount of water loss was estimated to be 8%. The second water loss at about 100°C may be due to the evaporation of unbound surface water. DT analysis identified a sharp endothermic phenomenon with an onset value of 170°C and a peak at 172°C.

[0202] like Fig.15As shown, TGA analysis of mode 2 shows an initial weight loss of 6.5% (0.9 equivalents of water), followed by sample degradation at about 280°C. The DT trace demonstrates an endothermic phenomenon associated with the initial weight loss. This is followed by an exothermic phenomenon at 118°C (recrystallization to mode 1). The second endothermic observed at 170°C and the peak at 172°C are considered to be sample melting. In other embodiments, the CHP hydrate of the present invention exhibits at least one endothermic phenomenon at about 75-85°C, which is dehydration. In another embodiment, the CHP hydrate of the present invention exhibits at least one exothermic phenomenon at about 115-about 120°C, which is a phenomenon of recrystallization into mode 1. E. Differential Scanning Calorimetry (DSC)

[0203] DSC was performed by weighing about 5 mg of material into an aluminum DSC pan and sealing it non-hermetically with a perforated aluminum lid. The sample pan was then placed in a Seiko DSC6200 (equipped with a cooler) and cooled and maintained at 20°C. Once a stable heat flow response was obtained, the sample and reference sample were heated to 250°C at a scan rate of 10°C / min and the resulting heat flow response was monitored. Nitrogen was used as a purge gas with a flow rate of 50 cm 3 / min.

[0204] like Fig.16 As shown, the first thermal cycle of mode 1 shows a small and broad endothermic peak starting at 75°C and peaking at 85°C. Fig.14 This is consistent with the 0.6% weight loss observed in TG / DTA. A second large endotherm is observed at 169°C and peaks at 171°C. This is consistent with the melt seen in TG / DTA. Fig.16 The first broad peak in is probably due to the dehydration of mode 2 to mode 1. Fig.16 The second peak in may be the melt of pattern 1.

[0205] like Fig.17 As shown in Figure 2, no thermal phenomena were observed during the cooling cycle. Fig.18 As shown, a very small broad peak was observed at about 80 °C in the second thermal cycle, a potential glass transition point.

[0206] like Fig.19 As shown, the first thermal cycle of mode 2 identified an endotherm starting at 99°C and peaking at 102°C. The sample was observed to melt starting at 170°C and peaking at 173°C. This is consistent with the data observed in TG / DTA. Fig. 20 As shown, no thermal phenomena were observed during the cooling cycle of Mode 2.

[0207] like Fig.21As shown, a possible glass transition point was observed at 77 °C in the second heating cycle of CHP hydrate.

[0208] In one embodiment, the CHP hydrate of the present invention exhibits an endotherm starting at about 75°C to about 100°C. F. Fourier Transform Infrared Spectroscopy (FT-IR)

[0209] FR-IR was performed on a Bruker ALPHA P spectrometer. Sufficient material was placed in the center of the spectrometer plate and the spectra were acquired using the following parameters: Resolution: 4 cm -1 , Background scan time: 16 scans, Sample scan time: 16 scans, Data collection: 4000-400cm -1 , result spectrum: transmittance, and software: OPUS version 6.

[0210] like Fig. 22 As shown, the FT-IR of mode 2 is consistent with the structure. The solid infrared spectrum of mode 2 shows signals at 3457, 3411 (m); 3292, 3211 (m); 2976; 1658; 1633 (m); and 1445-1424 (m) cm -1 In other embodiments, CHP and CHP hydrate of the present invention exhibit substantially the same IR spectra, which exhibit a wavelength from about 500 cm -1 to about 1660cm -1 At least nine bands. Mode 2 at 3457 and 3411 cm due to water in the lattice (hydrate) -1 has stretching, while mode 1 does not. G. Dynamic Vapor Sorption (DVS)

[0211] DVS was performed by placing about 10-20 mg of sample into a mesh vapor sorption balance pan and loading it into a DVS intrinsic dynamic vapor sorption balance through a surface measurement system. The sample was subjected to a ramping profile humidity increase from 40% to 90% relative humidity (RH) in increments of 10%, and the sample was kept at each step until a stable weight was obtained at 25°C (dm / dt 0.004%, minimum step length 30 minutes, maximum step length 500 minutes). After the adsorption cycle was completed, the sample was dried to 0% RH using the same procedure, and then a secondary adsorption cycle was returned to 40% RH. Two cycles were performed. The weight change during the adsorption / desorption cycle was plotted to consider the hygroscopicity of the sample. Any retained solid was then subjected to XRPD analysis.

[0212] like Fig.23As shown, the isotherm of DVS of mode 1 shows a 6.3% weight increase from 60% RH to 90% RH, indicating a transformation to CHP hydrate, mode 2. Fig.24 As shown in Figure 2, after transitioning to Mode 2, the material exhibits only a slight hygroscopicity with a maximum absorption of 0.8 wt% between 0% and 90% RH, which is believed to be surface water rather than part of the crystalline structure. Fig.25 As shown, the kinetic diagram of the DVS of mode 1 shows that mode 1 is initially hydrated to form mode 2, but does not lose water during the desorption stage, indicating that the slight weight increase of 0.8% is not part of the solid structure.

[0213] like Fig.26 As shown, the XRPD analysis of pattern 1 after DVS (post-DVS) showed a new form, which was identified as pattern 2. Fig. 27 As shown, TG / DTA analysis after DVS for mode 2 shows an initial weight loss of 6.8% (0.95 equivalents of water), followed by sample degradation at about 280° C. The DT trace identifies an endotherm associated with the weight loss, followed by recrystallization (for mode 1), an exotherm at about 120° C., and then melting starting at 168° C. and peaking at 172° C.

[0214] CHP Mode 2 was placed in several higher temperature conditions to test dehydration / rehydration at 0%-90% humidity: 25°C ( Fig.28 ); 40℃( Fig.30 ); 50℃( Fig.31 ); and 60°C ( Fig.32 ).

[0215] like Fig.28 As shown, the DVS isotherm shows that the Mode 2 material does not change between 40% to 90% RH and 10% to 90% RH. The material then loses 3.5% weight below 10% RH and rehydrates from 0% to 90% RH. Fig.29 As shown, the kinetic curve of DVS shows that CHP hydrate lost 3.5% of water (red line) during the desorption stage from 80% to 0% RH in 500 minutes. Fig.30 , 31 As shown in Figures 3 and 4, Mode 2 undergoes a single cycle at 40°C, 50°C, and 60°C. 40°C shows that the material begins to dehydrate below 10% RH, losing approximately 5.8 wt% (0.8 equivalent water) from 10%-0% RH. The material hydrates from 0% to 40% RH ( Fig.30 ). At 50°C, the material begins to dehydrate below 20% RH, losing approximately 6.1 wt% (0.8 equivalents of water) from 20% to 0% RH. The material rehydrates from 0% to 40% RH ( Fig.31 ). Analysis at 60°C showed that the material began to dehydrate below 20% RH, losing approximately 7 wt% (1.0 equivalent water) from 20% to 0% RH. The material rehydrated from 0% to 40% RH ( Fig.32 ).

[0216] In other embodiments, the CHP hydrate of the present invention exhibits a weight loss of about 3% to about 9%, or about 4% to about 8.5%, or about 5% to about 8%. In another embodiment, the CHP hydrate of the present invention exhibits a weight loss of about 5.5% to about 7.3%.

[0217] In yet another embodiment, the CHP hydrate of the present invention exhibits a weight loss of about 5.8% to about 7.0%. H. Variable Temperature and Humidity X-ray Powder Diffractometer (VT- / VH-XRPD)

[0218] VT- / VH-XRPD analysis was performed on the Mode 2 material. Mode 2 was initially scanned at 40% RH and ambient temperature. When the RH was reduced to 0% at ambient temperature, Run 2 remained as Mode 2. The temperature was raised to 80°C and the sample was left for 20 minutes before scanning. The resulting diffraction pattern indicated that the material produced was pure Mode 1. Pure Mode 1 remained after 80 minutes at 80°C and 0% RH. Fig.33 These results are shown.

[0219] Fig.34 XRPDs of Mode 2 materials after various VT / DVS are shown. In other embodiments, CHP hydrates of the present invention occur from at least about 0% to about 90% RH at room temperature. In another embodiment, 100% of Mode 2 transitions to Mode 1 at 80°C 0% RH. I. 1 H Nuclear Magnetic Resonance (NMR)

[0220] NMR was performed at 500.12 MHz (for protons) using a Bruker AVIIIHD spectrometer equipped with a DCH cryoprobe. Experiments were performed in deuterated DMSO and each sample was prepared at a concentration of about (ca.) 10 mM. Mode 1 CHP (DMSO-d 6 )of 1 H-NMR spectrum showed that the results were consistent with those of compound ( Fig.35 ) have the same structure. Fig.36 Provides model 2 (DMSO-d 6 )of 1 H-NMR spectrum. Mode 2 and mode 1 CHP show the same NMR spectrum, and both are completely dissolved in the solvent. Fig.37As shown, for dry material mode 2 ( Fig. 9 The dried material was subjected to NMR (pink line). No changes were observed compared to the Mode 2 feed.

[0221] In one embodiment, the CHP hydrate of the present invention exhibits 6 CHP-anhydrate in solvent is basically the same 1 H-NMR. J. Heteronuclear Single Quantum Coherence (HSQC) NMR

[0222] HSQC-NMR was performed on Mode 2 using a Bruker 500 MHz NMR instrument. DMSO-d 6 Used as NMR sample solvent. Fig.38 As shown, the results of mode 1 show that the chemical shift of the two imidazole CHs is 4.2 ppm.

[0223] For dry materials, Mode 2 ( Fig. 9 HSQC-NMR experiments were performed using the pink line. Fig.39 As shown, the results indicate that the NMR of the dried material (mixture of Mode 1 and Mode 2) and the Mode 2 material are identical. K. Freeze-dried

[0224] For solubility screening: 330 mg of CHP mode 1 was dissolved (under gentle heating) in water (3.3 mL) and aliquoted into 33 vials. The vials were then frozen at -50°C and then freeze-dried overnight. It is well known that freeze drying of crystalline compounds produces amorphous material that is generally more soluble than the crystalline form of a given compound.

[0225] like Fig.40 As shown, the material recovered from freeze drying of Mode 1 exhibited some crystalline peaks when analyzed by XRPD. Applicants believe that these initial peaks are indicative of a mixture of hydrate and anhydrous forms intermixed with the amorphous form.

[0226] For another round of freeze-drying, Fig.40 Each 10 mg sample was redissolved in 200 μL of water. The vials were frozen again at -50°C and then freeze-dried for 72 hours. The material recovered from freeze drying was mainly amorphous by XRPD analysis, such as Fig.41 shown.

[0227] For the amorphization test: CHP hydrate (mode 2) was dissolved in distilled water. The solution was aliquoted into 26 glass vials and the vials were frozen at -50°C in preparation for freeze drying. Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 48 hours. Fig.42 As shown, the material recovered from freeze drying of Mode 2 was found to be Mode 2 when analyzed by XRPD.

[0228] For another round of amorphization, the sample was redissolved by adding 1 mL of distilled water to each vial. The solution was then pipetted into 26 20 mL glass vials and capped with an additional 15 mL of distilled water. The vials were frozen at -50 °C and then freeze-dried for approximately 48 hours. After 48 hours, the sample was not completely freeze-dried and the vial was returned to the desiccator and freeze-dried for an additional 72 hours. The material analyzed by XRPD was found to still contain peaks of Mode 2.

[0229] In other embodiments, freeze drying of the CHP hydrate of the present invention shows that Mode 2 is more stable than Mode 1 and retains at least about 10% to about 40% purity after amorphization. L. Solubility screening

[0230] 33 x 10 mg samples of CHP mode 1 (anhydrous form) were lyophilized in 2 mL vials, and 100 μL of different solvent systems were added to each vial. Between each addition, the mixture was checked for dissolution, and if no dissolution was observed, the mixture was heated to about 40 ° C and checked again. After 300 μL of solvent was added, a 100 μL aliquot was added. This process was continued until dissolution was observed or until 1 mL of solvent was added. If dissolution did not occur, the solids were separated by filtration, collected and subjected to XRPD analysis. If dissolution occurred, the solvent was evaporated and any solids left were collected for XRPD analysis.

[0231] Fig.43 The approximate solubility of Mode 1 in various solvents is provided. Fig.44 The solvent solubility results for Mode 1 based on the volume of solvent added are provided. Fig.43 and 44 As shown, high solubility was observed in ethanol, methanol, N,N-dimethylacetamide, water, DMSO, trifluoroethanol, 1-propanol, and methanol / water mixtures. The samples were left uncovered to allow evaporation, and the observed solids were analyzed by XRPD.

[0232] like Fig.45As shown, XRPD analysis identified 2 unique patterns in addition to pattern 1 (crystalline form) from the kinetic solubility screen, although pattern 3 only appeared as a mixture with pattern 2. Acetone, dichloromethane (DCM), ethyl formate, and MtBE produced pattern 2 (hydrate form). A mixture of crystalline and hydrate forms was observed in ethanol. Chlorobenzene produced a mixture of patterns 2 and 3, and THF recovered mainly amorphous material with some peaks of pattern 2. A colorless gel was seen in methanol, which was not analyzed by XRPD. The solvent system produced crystals during evaporation and is considered a potential THF solvate.

[0233] like Fig.45 As shown, 9 of the 30 solvent systems listed produced insufficient solid for XRPD analysis. 16 solvents recovered Mode 2, Mode 1 was observed in 1-propanol, a mixture of Modes 1 and 2 was observed in ethanol, chlorobenzene produced a mixture of Modes 2 and 3, and THF produced primarily amorphous material with some Mode 2 peaks.

[0234] Fig.46 Primary polymorph screening solvents are described.

[0235] In other embodiments, the CHP hydrate of the present invention can be produced by kinetic crystallization (2-6 hours) from 1-propanol, 2-propanol, methanol / water mixtures, acetone, acetonitrile, ethyl acetate, ethyl formate, heptane, isopropyl acetate, methyl ethyl ketone (MEK), methyl isobutyl ketone, nitromethane, toluene, and trifluoroethanol. M. Primary Polymorph Screening

[0236] To 24 vials containing 40 mg of anhydrous CHP, different solvents were added in 100 μL aliquots until a thin slurry was observed. The vials were then temperature cycled between ambient temperature and 40° C. in 4 hour cycles over 72 hours. Any remaining solids were separated by centrifugation and analyzed by XRPD.

[0237] Fig.46 Solvents used for kinetic (2-6 hours) polymorph screening are shown. Fig.50 The primary polymorph screening temperature cycle for Mode 1 is shown.

[0238] The results show that when water is present in the sample, mode 2 is dominant. Mode 1 is formed only when insufficient water is present in the sample, where the water comes from the sample itself, the solvent system, or is adsorbed from the atmosphere. These results are summarized in Tables 24 and 25. Example 2- Preparation of CHP Hydrate

[0239] This study was conducted to (1) evaluate the conversion process of Mode 1 (anhydrous, C16081735-D) to Mode 2 (hydrate, Mode 2); (2) evaluate a demonstration run at an approximately 100-gram scale using non-GMP CHP Mode 1 (anhydrous) stored by a designated manufacturer; (3) produce approximately 400 g of Mode 2 under current good manufacturing practice (cGMP) regulations; and (4) evaluate drying conditions to ensure that the desired Mode 2 (hydrate, Mode 2) is obtained.

[0240] The specifications are set as follows: HPLC purity: ≥98.0%; impurity distribution: H-His-OH ≤1.0%, each independently ≤1.0%; chiral purity: ≥98.0%; chiral impurities: report each impurity ≥0.1%; DL, LD, LL optical isomers ≤1.0%, etc.

[0241] A reproducible method was developed for the preparation of Model 1 (anhydrous) by dissolving it in EtOH / H 2 Mode 2 (cyclo(L-His-L-Pro) dipeptide hydrate) was prepared by adding MtBE to precipitate Mode 2 (hydrate). This method has been successfully implemented on a 370 g scale cGMP batch. Finally, a total of 288 g of Mode 2 (CHP hydrate) with 99.9% HPLC purity and 100.0% chiral purity was produced under cGMP conditions. A. Introduction to the Synthesis Scheme

[0242] The method of converting mode 1 (anhydrous) to mode 2 (hydrate, mode 2) was evaluated. Two crystallization methods were provided, one was to dissolve the anhydrous solid in water and precipitate by adding acetone (see Synthesis Scheme 1); the other was to dissolve the anhydrous solid in EtOH / water = 9 / 1 and precipitate by adding MtBE (see Synthesis Scheme 2). The quality and yield of the two processes were evaluated, and Scheme 2 was determined for optimization work. Finally, the optimized method (see Scheme 3) was successfully implemented to produce 288 g of Mode 2 (CHP hydrate). The production process followed Scheme 3. Scheme 1: The first synthetic route of synthetic mode 2 (CHP hydrate) Scheme 2: Second synthetic route of synthetic mode 2 (CHP hydrate) Scheme 3: Optimized synthetic route of Model 2 (CHP hydrate) for cGMP production

[0243] Two processes (Schemes 1 and 2) were evaluated, and the product was a hydrate with the target mode 2. The chemical stability under both conditions was studied, and mode 2 was stable for 20 hours at 50°C. However, the water / acetone process uses a very small amount of water (1v) as a good solvent, and it is difficult to select a suitable reactor with such a small minimum stirring volume. In addition, the water / acetone process only gave an isolated yield of about 70%. The EtOH / H 2 The O / MtBE process was used for optimization work with an isolated yield of approximately 90%.After the optimized crystallization process, cGMP batch production at 370 g scale was successfully carried out in a kilo-lab. B. Summary

[0244] For the preparation of Mode 2, water / acetone and EtOH / H 2 Two crystallization procedures of O / MtBE were performed, both of which gave products as hydrates with target mode 2. The chemical stability under both conditions was studied, and the product was stable at 50 °C for 20 h. Considering that the water / acetone procedure only produced about 70% isolated yield, the EtOH / H2O process was selected. 2 The O / MtBE process was used for optimization work. The addition temperature and addition rate of MtBE were studied, and the addition of MtBE was completed at a relatively slow rate at 5°C to avoid large amounts of solids adhering to the walls of the container. Following the optimized crystallization process, a single experiment on a 100 g scale successfully crystallized 96.44 g of Mode 2 product with an isolated yield of approximately 90%. Based on drying stability studies, the hydrate product was stable below 40°C in a laboratory oven at -0.09 MPa.

[0245] C. Evaluation of the Crystallization Process under Water / Acetone Conditions

[0246] Two experiments were conducted to evaluate the RFP crystallization process using water / acetone conditions (Table 2). No crystallization was observed in the absence of seeds in experiment PS03027-2, and solids precipitated after seed addition. Seeds were added in experiment PS03027-4 and crystallization proceeded smoothly. XRPD showed that the target pattern 2 was obtained. The product loss in the water / acetone system was relatively high (about 20%), which is consistent with the yield of RFP (72%). Table 2. Preparation results of CHP hydrate NOTE: Seed crystals were prepared by reslurrying Pattern 1 in 1 volume of water at room temperature. D. Evaluation of an Alternative Crystallization Scheme Using EtOH / Water / MTBE

[0247] A 5 g scale batch was run to evaluate the alternative EtOH / water / MTBE crystallization conditions, crystals nucleated during the MtBE addition and XRPD showed that the target pattern 2 was obtained. The losses in the mother liquor were relatively low (8%) compared to the water / acetone condition (Table 3). Table 3. Preparation results of CHP hydrate E. Study on chemical stability in water / acetone and EtOH / water / MtBE

[0248] The solution state chemical stability of the compound was studied in different solvent systems at different temperatures (Table 4). The solution was maintained at 50°C and 80°C and the purity of the solution was followed. The compound was generally stable for at least 20 hours. Table 4. Chemical stability in water / acetone and EtOH / water / MtBE F. Study on the solubility of CHP hydrate (Model 2)

[0249] The solubility of CHP hydrate in water / acetone and EtOH / water / MtBE was studied and found to be sensitive to solvent ratio and temperature under both conditions (Tables 5 and 6). The yield in EtOH / water / MtBE crystallization was 90% or higher. Table 5. Solubility of Mode 2 in water / acetone Table 6. Solubility of Model 2 in EtOH / Water / MtBE Note: 1) Lot number PS03027-2-H is used as Mode 2 material. G. Process Optimization of EtOH / Water / MtBE Conditions

[0250] To further understand crystallization in EtOH / water / MtBE, three experiments were performed in which MtBE was added at 50° C., 35° C., and 5° C. As shown in Table 7, the three experiments provided the desired crystalline form with low residual solvent. Table 7. Process Optimization in EtOH / Water / MtBE (5 g Scale)

[0251] To validate the process at a larger scale, three 15 g scale experiments were performed, as shown in Table 8. During experiments PS03027-13 and PS03027-14, where MtBE was added at 50°C and 35°C, a crusting problem was observed. A large amount of solids adhered to the walls of the vessel, especially during the MtBE addition. To avoid this problem, in experiment PS0027-15, MtBE was added at 5°C and the addition was extended to 8 hours (4 hours in the previous experiments). Much less crusting on the walls was found. It was therefore concluded that MtBE should be added at a relatively slow rate at 5°C. Table 8. Process Optimization in EtOH / Water / MtBE (15 g Scale) H. Rapid addition of stress test for MtBE

[0252] The process was stress tested with MtBE addition at a relatively fast rate as shown in Table 9. The XRPD of the solid was followed during the experiment and the data indicated that Pattern 2 was observed throughout the crystallization process. Table 9. Stress test of rapid addition of MtBE I. Study of Form Stability in EtOH / Water / MtBE

[0253] To investigate the form stability in EtOH / water / MtBE, competitive replicates were performed at 50°C, 35°C, and 5°C by adding 100 mg of anhydrous Mode 1 solid and 100 mg of Mode 2 solid. As shown in Table 10, the mixed form of Mode 1 and Mode 2 rapidly transformed into Mode 2 under different conditions. Table 10. Competitive slurries of Mode 1 and Mode 2 in EtOH / water / MtBE Note: Feed: 100 mg of anhydrous solid (Mode 1, Batch #PS00726-55-D) was added along with 100 mg of Mode 2 solid (Batch #PS03027-5 / 9 / 10 / 11-H). J. Study on drying stability at 35℃, 40℃, 50℃ and 65℃

[0254] Drying stability was tested at 35° C., 40° C., 50° C. and 65° C. As shown in Table 11, Pattern 2 was stable up to 40° C. for at least 4 days. Table 11. Drying stability at 35°C, 40°C, 50°C and 65°C K. Study the slurry process to convert the poor crystals back to Mode 2

[0255] The cGMP batch for Mode 2 (Mode 218001) had low crystallinity due to overdrying (KF = 5.4%, theoretical value is 7.4%), even when dried at 35-40°C for 10 hours. In order to convert the poor crystalline Mode 2 solid to the desired Mode 2, two reslurry experiments were performed. At RT and 5°C, 2g of Mode 218001-STEP5.7 was reslurried in 8 volumes of EtOH / water / MtBE = 9v / 1v / 30v and found to be converted to Mode 2 in only 30 minutes. The solid was separated and dried for 14 hours, during which time the form remained unchanged. The loss based on the mother liquor concentration was about 5% (while the expected total loss was 10%, including losses on the flask walls and in operation). One advantage is that this process achieves conversion of all solids to Mode 2, although about 10% of the product may be lost. L. General route from Mode 1 to Mode 2 1. In N 2 EtOH (1.75-1.79X; 2.25v) was added to R1 2. In N 2 Add purified water (0.245-0.255X; 0.25V) to R1 3. Stir R1 for 5-10 minutes to obtain a mixed solution of EtOH / water = 9:1 (v / v). 4. Transfer the solution from R1 to the drum 5. Add Mode 1 (1.0 equiv., 1.0X) to R1. 6. In N 2 Under 4% CO, add the EtOH / water mixture (1.61-1.63X, 2.0V) from step 4 to R1 7. In N 2 Adjust R1 to 47-53°C. 8. In N 2 R1 was stirred at 47-53°C for 10-60 minutes. 9. Polish filter the solution from R1 to R2. Preheat the jacket of R2 to 50-55°C. 10. In N 2 Under 4% CO, the EtOH / water mixture (0.39-0.41X; 0.5V) from step 4 was added to R1 11. In N 2 Stir R1 for 5-30min 12. Fine filter the solution from R1 to R2 13. Adjust R2 to 47-53℃ and heat at N 2 Stir for 10-60 minutes. Complete dissolution is confirmed by the project leader. 14. In N 2 Adjust R2 to 32-37°C. 15. In N 2 MtBE (0.36-0.38X; 0.5 V) was slowly added to R2 at 32-37 °C. 16. At 32-37°C, add Pattern 2 seeds (0.015-0.025X) to R2. 17. In N 2 R2 was stirred at 32-37 °C for 2-3 h. 18. In N 2 Adjust R2 to 3-8°C within 2-3 hours. 19. Take a sample and filter, and send the filter cake for XRPD analysis: XRPD (consistent with PS03027-15-H). Criteria: If the results meet the specifications, proceed to step 20; otherwise, consult the project leader. 20. In N 2 MtBE (5.1-5.3X; 7v) was added to R2 at 3-8°C over 8 hours. 21. In N 2 R2 was stirred at 3-8°C for 8-10 h. 22. Sampling and filtration, send filter cake for XRPD analysis: XRPD (consistent with PS03027-15-H); send filtrate for residual mode 2 analysis: residual H in supernatant (≤1.5% w / w). Standard: If the result meets the specification, go to step 25; otherwise, go to step 23. 23. In N 2 R2 was stirred at 3-8°C for 4-10 h. 24. Sampling and filtration, send filter cake for XRPD analysis: XRPD (consistent with PS03027-15-H); send filtrate for residual H analysis: residual H in supernatant (≤1.5% w / w). Criteria: If the result meets the specification, proceed to step 25. 25. In N 2 The suspension was filtered at 3-8°C under atmospheric pressure. 26. Place EtOH (0.355X), purified water (0.05X) and MtBE (1.11X) into a clean drum. 27. Stir the material in step 26 to obtain a clear mixture solution. 28. Transfer the solution (1.5-1.6X) from step 27 to R2 to rinse R2. 29. Cool R2 to 3-8℃. 30. Wash the wet cake with R2 rinse solution at 3-8°C. 31. Check the quality of wet products: XRPD (consistent with PS03027-15-H); HPLC ≥ 98.0% area; H-His-OH ≤ 1.0% area, each other individual ≤ 1.0% area; report each impurity ≥ 0.05% area with RRT Note: Perform step 32 in parallel. Criteria: If the result meets the specification, proceed to step 33. 32. Check the remaining mode 2 in the mother liquor. Report the remaining amount of mode 2 (%). 33. Vacuum dry at 35-40°C for 10-12 hours. It is recommended to have a built-in water bath in the oven to avoid over-drying. 34. Check residual solvents: EtOH (≤5000ppm); MtBE (less than or equal to 5000ppm); Water content (report) Check the polymorph of the dried product: XRPD (consistent with PS03027-15-H) Standard: If the result meets the specification, proceed to step 37; otherwise, proceed to step 35. 35. Vacuum dry at 35-40°C for 5-8 hours. It is recommended to have a built-in water bath in the oven to avoid over-drying. 36. Check residual solvents: EtOH (≤5000ppm); MtBE (less than or equal to 5000ppm); Water content (report) Check the polymorph of the dried product: XRPD (consistent with PS03027-15-H) Criteria: If the result meets the specification, proceed to step 37. 37. The dried product is loaded into buckets and sieved. 38. Take samples for release analysis. M. Comprehensive Characterization HPLC purity, 1 The HNMR, TGA, DSC and XRPD spectra are shown in Table 12. Table 12: Characterization of Mode 2 Example 3 - Crystallization Process Development of Hydrated CHP

[0256] The research focused on the crystallization development of CHP hydrate (mode 2). After the initial characterization of a batch of CHP hydrate, solubility studies, small-scale crystallization evaluation, metastable zone width measurements and scaled-up crystallization were performed. The aim of the work program was to establish crystallization conditions in order to successfully produce CHP hydrate mode 2, which can be effectively scaled up for production.

[0257] Solubility evaluation of CHP Mode 1 showed high solubility in all aqueous solvent mixtures except ethanol:water:MtBE spiked with the highest percentage of MtBE. Particularly high solubility was observed with water (≥200 mg / mL) and acetone:water blends (≥200 in water:acetone [90:10]). Very poor solubility was observed in acetone, acetonitrile, and THF (≤10 mg / mL).

[0258] The two-point solubility shows that, of the two solvent systems evaluated, ethanol:water:MtBE allows slightly higher yields, but at the risk of forming mode 1. Acetone:water only allows the formation of mode 2, but at the expense of yield.

[0259] In one embodiment, the following method is provided to prepare CHP hydrate: • Add approximately 20 g of CHP mode 1 to a jacketed reaction vessel and preheat to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. • Stir using an overhead stirrer at 300 rpm. • When complete dissolution was achieved, 25 mL of MtBE was added to the vessel (dropwise). - After the MtBE addition was complete, the experiment was seeded with 2 wt% (400 mg) of ground Crystallization Mode 2 CHP. Continue stirring at 50°C for 20 minutes. - Add another 5 mL of MtBE to the vessel (dropwise). • Add 70 mL of MtBE at a rate of 20 mL / hour. When addition is complete, cool from 30°C to 29°C at 0.1°C / min. Continue stirring at 29°C for 8 hours. Cool from 29°C to 5°C at a rate of 0.25°C / min. · Add 190 mL of MtBE at a rate of 20 mL / hour. Continue stirring at 5°C for 12 hours - Isolate the solids by filtration and wash the filter cake with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol). - Dry the solid under vacuum at 40°C for 1 hour.

[0260] An estimate of the mixing performance at the laboratory scale was performed and then modeled at the plant scale geometry to estimate the configuration parameters that would allow the process to be successfully transferred. Transfer of the process to the 10 kg scale could be performed using the following process: • Add approximately 10 kg of CHP mode 1 into a jacketed reaction vessel and preheat to 50°C. • Add 25 L of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. Stir at 48 rpm. When complete dissolution was achieved, 12.5 L of MtBE was added to the vessel. • After the MtBE addition was complete, the experiment was run with 2 wt% (200 g) of ground Crystallization Mode 2 CHP seeds. Continue stirring at 50°C for 20 minutes. - Add another 2.5 L of MtBE to the vessel (dropwise). · Add 35 L of MtBE at a rate of 10 L / hour. When addition is complete, cool from 30°C to 29°C at 0.1°C / min. Continue stirring at 29°C for 8 hours. Cool from 29°C to 5°C at a rate of 0.25°C / min. · Add 95 L of MtBE at a rate of 10 L / hour. Continue stirring at 5°C for 12 hours - Isolate the solids by filtration and wash the filter cake with 20 L of ethanol:water:MtBE (9 vol:1 vol:30 vol). - Dry the solid under vacuum at 40°C.

[0261] It is recommended to use 48 rpm as this allows the power dissipation in the plant scale vessel to be more consistent with the power dissipation of the laboratory scale vessel. The power dissipation in the plant was estimated to be 0.067 W / kg, while at the laboratory scale, the power dissipation was estimated to be 0.064 W / kg. The model used to estimate these parameters also estimates that the particles are likely to be suspended.

[0262] Alternatively, the plant's agitator may be running at 55 rpm. This has been estimated by the mixing model as the critical suspension speed (NJS), the just suspended mixing speed where the particles will be suspended in the container. This increases confidence that the binding is effective, however there is a risk that the particles will experience a much higher power dissipation of 0.101 W / kg.

[0263] However, it should be understood that one or more of the above steps for obtaining CHP hydrate may be omitted, or the order of the steps may be changed. B. Analytical Methods 1. X-ray powder diffraction (XRPD)

[0264] XRPD analysis was performed on a PALAYLIC X'PERT pro, scanning the samples between 3 and 35° 2θ. The material was lightly ground to loosen any agglomerates and loaded onto a porous plate with a Mylar polymer film to support the sample. The porous plate was then placed in the diffractometer and the Cu K radiation source (α1 The analysis was performed in transmission mode (with a step size 2θ of 0.0130°) using a 40 kV / 40 mA generator setup. 2. Polarized Light Microscopy (PLM)

[0265] The presence of birefringence, particle size and morphology were evaluated using an Olympus BX50 polarizing microscope equipped with a Motic camera and image capture software (Motic Images Plus 2.0). Unless otherwise stated, all images were recorded using a 20x objective. 3. Thermogravimetric analysis (TGA)

[0266] About 5 mg of material was weighed into an open aluminum pan and loaded into a coupled thermogravimetric / differential thermal analyzer (TG / DTA) and kept at room temperature. The sample was then heated from 20°C to 350°C at a rate of 10°C / min, during which the change in sample weight and any differential thermal phenomena (DTA) were recorded. Nitrogen was used as a purge gas with a flow rate of 300 cm 3 / min. 4. Nuclear Magnetic Resonance (NMR)

[0267] NMR was performed at 500.12 MHz (for protons) using a Bruker AVIIIHD spectrometer equipped with a DCH cryoprobe. Experiments were performed in deuterated dimethyl sulfoxide, with each sample prepared at a concentration of approximately 10 mM. 5. Focused beam reflectance measurement (FBRM)

[0268] Focused beam reflectance measurements were performed using a Mettler Toledo D600 probe. For each crystallization, the probe was placed into the reaction vessel at the start of crystallization and nucleation and crystal growth were monitored. Chord length distribution and various counting statistics were always monitored using the following settings: Electronic identification rangefinder Scan speed 2ms -1 Sampling time 10s 6. Crystallizer (Crystal 16)

[0269] The Crystal 16 (parallel crystallizer) instrument uses the percent transmission of light through a solution (or slurry) in a transparent vial to establish a turbidity curve of the solution (or slurry) as a function of time and temperature. The curve obtained is used to determine the cloud point (nucleation temperature) and the clearing point (dissolution temperature). 7. High performance liquid chromatography-ultraviolet detection (HPLC-UV)

[0270] HPLC analysis was performed using the following equipment parameters: Instrument: Dionex Ultimate 3000 Chromatographic column: LC / 168X-Bridge Phenyl Column (150mm×4.6mm×3.5μm) Column temperature: 30°C Autosampler temperature: 5°C UV wavelength: 220nm Injection volume: 5 μL Flow rate: 1mL / min Mobile phase A: 10 mM ammonium acetate Mobile phase B: acetonitrile Diluent: 0.1% TFA in water Gradient Program: C. Experiment 1. Initial Characterization of CHP Mode 1

[0271] Following the procedures detailed in Part B, 1 H-, HSCQ- and 13 C-NMR and HPLC characterization of CHP pattern 1. 2. Approximate solubility of CHP mode 1 (anhydrous)

[0272] The approximate solubility of CHP in 37 selected solvent systems was estimated by solvent addition technique (Table 13). The following procedure was used: • Approximately 20 mg of CHP Mode 1 was weighed into each of 37 vials. • Each solvent / solvent mixture was added in 5 volume aliquots (100 μL) to the appropriate vial until dissolution was observed or a maximum of 2 mL of solvent was added. • Between additions, samples were heated to 40°C to check dissolution at elevated temperature. If the substance does not dissolve after adding 2 mL of solvent, the solubility is estimated to be less than 10 mg / mL. - After solvent addition, all 37 vials were flash cooled in a refrigerator between 2-8°C for approximately 18 hours. • Any solids present were separated by centrifugal filtration and analyzed by XRPD (allowing for the amount of material). In the event that no solids were produced, the vial was uncapped and allowed to evaporate at ambient temperature. - Any solids present (where material allowed) were analysed by XRPD. Table 13: List of solvents with approximate solubility 3. Two-point solubility

[0273] Two-point solubility studies were performed in 11 solvent mixtures at 5°C and 50°C using the following procedure: 1 mL of the selected solvent mixture was added to a 1.5 mL screw-top glass vial containing a pre-weighed mass of CHP Mode 1 to prepare a slurry. The initial mass selected for each solvent system was based on the approximate solubility found as detailed in Section 2. The solvent blends are shown in Table 14. - The vials were maintained in a thermostatically controlled reaction zone set at either 5°C or 50°C, with agitation provided by a magnetic stirrer plate. • Where complete dissolution was observed after 1 hour, more CHP Mode 1 solid was added to the experiment to form a slurry. • When a flowing slurry was formed in all vials, the experiment was stirred at the desired temperature for about 18 hours. The final mass of CHP Mode 2 required is shown in Table 14. - After about 18 hours, stop stirring and filter the supernatant using a 0.45 μm PVDF syringe filter and a syringe. - The concentration of the supernatant was analyzed by HPLC. • Transfer the remaining slurry in the vials to each 0.22 μm nylon filter centrifuge tube and separate the solids by centrifugation. - The purity of the recovered solid (amount allowed) was analyzed by XRPD and HPLC. Table 14: Final CHP mass for two-point solubility 4. Small-scale crystallization

[0274] Small scale crystallization trials were performed on the obtained CHP (pattern 1). The purpose of these trials was to investigate the most suitable solvent system, temperature and concentration for further crystallization studies. This was performed using two different solvent systems: acetone: water and ethanol: water: MtBE.

[0275] Crystallization group A: acetone: water - Approximately 500 mg of the resulting CHP (Mode 1) was weighed into 4 x 20 mL scintillation vials. Add appropriate volume of acetone:water (80:20 v / v%) to each vial to dissolve the sample. See Table 15 for the solvent volumes used. • A stir bar was added to each vial and the experiment was stirred at 50 °C. • After 1 hour at 50°C, acetone was added dropwise to 2 of the four vials (vials 1 and 3). • The experiment was stirred at 50°C for approximately 1 hour. After 1 hour, the vial was cooled to 5°C at a rate of 0.25°C / min. • Once at 5°C, add acetone dropwise to the remaining 2 vials (vials 2 and 4). The experiment was stirred at 5°C for about 18 hours. - After 18 hours at 5°C, the resulting slurry was then filtered using a 47 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 42.5 mm, pore size = 11 μm). • The solid was transferred to a pre-weighed vial and analyzed for chemical purity by XRPD, PLM and HPLC. The mother liquor after filtration was subjected to HPLC concentration analysis. The experiments are summarized in Table 15.

[0276] Crystallization group B: ethanol: water: MtBE - Approximately 500 mg of the resulting CHP (Mode 1) was weighed into 5 x 20 mL scintillation vials. • Add 2 mL of ethanol:water (90:10 v / v%) to each vial to dissolve the sample. • Add a stir bar to each vial and stir the experiment at 50 °C. - After 1 hour at 50 °C, MtBE was added dropwise to 3 of the five vials (vials 1, 3, and 5). The experiment was stirred at 50°C for about 1 hour. - After 1 hour at 50°C, the slurry present in vial 1 was filtered using a 47 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 42.5 mm; pore size = 11 μm). As the previous results of the experiments with filtration at 50°C showed, at this percentage of MtBE (80%) there is a potential risk of forming mode 1 after cooling. - Cool the remaining vials to 5°C at a rate of 0.25°C / min. • Once 5 °C was reached, MtBE was added dropwise to the remaining 2 vials (vials 2 and 4). The experiment was stirred at 5°C for about 18 hours. - After 18 hours at 5°C, the resulting slurry was then filtered using a 47 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 42.5 mm, pore size = 11 μm). • All solids were transferred to pre-weighed vials and analyzed for chemical purity by XRPD, PLM and HPLC. The mother liquor after filtration was subjected to HPLC concentration analysis. The experiments are summarized in Table 15. Table 15 Summary of solvents for small-scale crystallization 5. Metastable Zone Width (MSZW) Measurement

[0277] MSZW measurements were performed on the resulting CHP (mode 1) by studying two parameters - cooling and anti-solvent addition. Cooling method The determination of MSZW was done by cooling using a Crystal 16 (parallel crystallizer). The method used is summarized as follows: • Weigh a known amount of CHP (Mode 1) into a screw cap vial. • Add 1 mL of the appropriate solvent system to each vial to form a slurry. Place a stir bar in each vial. The solvent systems and masses of CHP used in each experiment are summarized in Table 16. The vials were placed in the sample holder of the Crystal 16 instrument and the desired temperature program was started. The temperature profile can be seen in Table 17A. Monitors the turbidity of the system throughout and allows determination of clear and cloud points. Table 16 Experimental details of cooling determination of MSZW Table 17: Temperature distribution of MSZW in cooling measurement a. Anti-solvent addition method

[0278] Determination of MSZW relative to antisolvent addition was done using ethanol:water:MtBE. The following procedure was used: • Approximately 20 g of the resulting CHP Mode 1 was transferred into a 250 mL jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 40 minutes), 75 mL of MtBE was added at a rate of 10 mL / hour via a peristaltic pump. • Upon completion of the MtBE addition, the experiment was cooled to 5°C at 0.25°C / min and held at 5°C overnight. • After 9 hours at 5°C, the solids were isolated by vacuum filtration using an 83 mm Buchner funnel and Whatman grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). • Take a sample of the filter cake and analyze by XRPD. The remaining filter cake was dried under vacuum at 35°C for 1 hour. The concentration of the mother liquor after filtration was measured by HPLC. 6. Crystallization Development

[0279] Crystallization scale-up experiments were performed in ethanol:water:MtBE. Various experimental conditions were evaluated, such as cooling rate, antisolvent addition rate and temperature, seeding load and temperature, and antisolvent ratio. The following schemes were considered:

[0280] a. Crystallization 1

[0281] For Crystallization 1, the solution was seeded with 2 wt% seed crystals. Seeding and MtBE addition were performed at 35 °C and the slurry was cooled to 5 °C at a rate of 0.25 °C / min. The following procedure was used: • Transfer approximately 20 g of the resulting CHP mode 1 into a jacketed vessel, which has been preheated to 50° C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture into the vessel to reach a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 30 minutes), the chamber was cooled to 35°C at a rate of 0.25°C / min and 10 mL of MtBE was added at a rate of 10 mL / h via a peristaltic pump. - Upon completion of MtBE addition, seed the experiment with 400 mg CHP Mode 2; monitor the system at 35 °C for approximately 2 hours. • The experiment was then cooled to 5°C at 0.25°C / min and 140 mL of MtBE was added via a peristaltic pump at a rate of 10 mL / hour (14 hours) to give a final solvent ratio of 25:75 v / v%. • The solids were isolated by vacuum filtration using an 83 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. Analyze the dried solids by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0282] b. Crystallization 2

[0283] For Crystallization 2, the solution was seeded with 2 wt% seed crystals. Seeding and MtBE addition were performed at 50 °C and the slurry was cooled to 5 °C at a rate of 0.25 °C / min. The following procedure was used: About 20 g of the obtained CHP mode 1 was weighed and transferred into a jacketed container preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 min), the experiment was maintained at 50 °C and 10 mL of MtBE was added at a rate of 10 mL / h via a syringe pump; - Upon completion of MtBE addition, seed the experiment with 400 mg CHP Mode 2; monitor the system at 50 °C for approximately 2 hours. - 140 mL of MtBE was added via a peristaltic pump at a rate of 20 mL / hour to give a final solvent ratio of 25:75 v / v%. The experiment was then cooled to 5°C at 0.25°C / min and maintained at 5°C for approximately 9 hours; - After 9 hours at 5°C, the solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solid was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0284] c. Crystallization 3

[0285] For Crystallization 3, the solution was seeded with 2 wt% seed crystals. Seeding and MtBE addition were performed at 35°C and the slurry was cooled to 5°C at a rate of 0.25°C / min. The following procedure was used: About 20 g of the obtained CHP mode 1 was weighed and transferred into a jacketed container preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 minutes), the experiment was cooled to 5°C at a rate of 0.25°C / min°C; Once the system reached 23°C, nucleation was observed; Heat the system to 50°C to redissolve the material. Once dissolution is observed, cool the system to 25°C at a rate of 0.25°C / min Once the system reaches 25 °C, nucleation is observed; Heat the system to 50°C to redissolve the material. Once dissolution is observed, cool the system to 35°C and seed the experiment with 400 mg CHP Mode 2; 140 mL of MtBE was added via a peristaltic pump at a rate of 20 mL / hour to give a final solvent ratio of 26:74 v / v%; The experiment was then cooled to 5°C at 0.25°C / min and maintained at 5°C for approximately 9 hours; • The solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. • The purity of the dried solid was analyzed by XRPD, TG / DTA, PLM and HPLC. The concentration of the mother liquor after filtration was measured by HPLC.

[0286] d. Crystallization 4

[0287] For crystallization 4, the solution was seeded with 2 wt% seed crystals. Seeding and MtBE addition were performed at 50 °C and the slurry was cooled to 5 °C at a rate of 0.1 °C / min. The following procedure was used: - About 20 g of CHP Mode 2 (material recovered from crystallizations 1 and 3) was weighed and transferred to a jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 min), the experiment was maintained at 50 °C and 20 mL of MtBE was added via a syringe pump at a rate of 20 mL / h; After the addition of MtBE was complete, a 400 mg CHP mode 2 seeding experiment was performed. Monitor the system at 50°C for approximately 2 hours; - 140 mL of MtBE was added via a peristaltic pump at a rate of 20 mL / hour to give a final solvent ratio of 24:76 v / v%. The experiment was then cooled to 5°C at 0.1°C / min; Keep the system at 5°C overnight; - After 8 hours at 5°C, the solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solids was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0288] e Crystal 5

[0289] For crystallization 5, the solution was seeded with 2 wt% ground seeds. Seeding and MtBE addition were performed at 50 °C, and the slurry was cooled to 5 °C at a rate of 0.1 °C / min. The following program was used: - Approximately 20 g of CHP Mode 1 and 2 blend (Mode 1 from the obtained CS / 352 / 18, Mode 2 from Crystallization 4) was weighed and transferred to a jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution is achieved (approximately 20 minutes), the experiment is maintained at 50 °C and 25 mL of MtBE is added dropwise using a syringe; After the addition of MtBE was complete, the experiment was seeded with 400 mg of CHP Mode 2 crystals that had been ground using a pestle and mortar. Monitor the system for approximately 75 minutes at 50°C; - 140 mL of MtBE was added via a peristaltic pump at a rate of 20 mL / hour to give a final solvent ratio of 23:77 v / v%. The experiment was then cooled to 5°C at 0.1°C / min; Keep the system at 5°C overnight; - After 9 hours at 5°C, the solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solids was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0290] f. Crystallization 6

[0291] For crystallization 6, the solution was seeded with 2 wt% ground seed crystals. Seeding was performed at 50°C and using staged addition of MtBE. The slurry was cooled to 29°C at a rate of 0.1°C / min and held at that temperature for 8 hours. The slurry was then cooled to 5°C at a rate of 0.25°C / min. The following procedure was used: - Weigh approximately 20 g of CHP Mode 1 and 2 blend (Mode 1 from as-obtained CS / 352 / 18, Mode 2 from Crystallization 5) and transfer to a jacketed vessel that has been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution is achieved (approximately 20 minutes), the experiment is maintained at 50 °C and 25 mL of MtBE is added dropwise using a syringe; After the addition of MtBE was complete, 400 mg of CHP mode 2 seed crystals that had been ground using a pestle and mortar were used for the experiment; Monitor the system at 50°C for approximately 10 minutes; • Seed crystals did not persist. An additional 5 mL of MtBE was added dropwise to the vessel using a syringe. 70 mL of MtBE was added at a rate of 20 mL / h via a peristaltic pump. The experiment was then cooled to 29°C at 0.1°C / min. The system was kept at 29°C for 8 hours. After 8 hours at 29°C, the system was cooled to 5°C at a rate of 0.25°C / min. Once the system reaches 5°C, start the second step of MtBE addition. Add 190 mL at a rate of 20 mL / hour. The final solvent ratio is 15:85 v / v%. • Keep the system at 5°C for about 12 hours. • The solids were then isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. • The dried solid was analyzed for purity by XRPD, TG / DTA, PLM and HPLC and chiral HPLC. The concentration of the mother liquor after filtration was measured by HPLC.

[0292] g. Crystallization 7

[0293] For crystallization 7, the solution was seeded with 2 wt% ground seeds. Seeding was performed at 50 °C and using staged addition of MtBE. The slurry was cooled to 5 °C at a rate of 0.1 °C / min. The following procedure was used: - Approximately 20 g of CHP Mode 1 and 2 blend (Mode 1 from as-obtained CS / 352 / 18, Mode 2 from Crystallization 6) was weighed and transferred to a jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 minutes), the experiment was maintained at 50 °C and 27.5 mL of MtBE was added manually (dropwise) using a syringe; After the addition of MtBE was complete, 400 mg of CHP Mode 2 ground with a pestle and mortar was used for seeding experiments; Monitor the system at 50°C for approximately 10 minutes; 70 mL of MtBE was added at a rate of 20 mL / h via a peristaltic pump. The experiment was then cooled to 5°C at 0.1°C / min; • Keep the system at 5°C overnight. After about 9 hours at 5°C, the second step of MtBE addition was started. 190 mL was added at a rate of 20 mL / hour. The final solvent ratio was 15:85 v / v%. • The solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solids was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0294] h. Crystallization 8

[0295] For crystallization 8, the solution was seeded with 5 wt% ground seeds. Seeding was performed at 50 °C and using staged addition of MtBE. The slurry was cooled to 5 °C at a rate of 0.1 °C / min. The following procedure was used: - Approximately 20 g of CHP Mode 1 and 2 blend (Mode 1 from as-obtained CS / 352 / 18, Mode 2 from Crystallization 7) were weighed and transferred to a jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 minutes), the experiment was maintained at 50 °C and 27.5 mL of MtBE was added manually (dropwise) using a syringe; When the addition of MtBE was complete, 1 g of CHP Mode 2 ground with a pestle and mortar was used for seeding experiments; Monitor the system at 50°C for approximately 10 minutes; 70 mL of MtBE was added at a rate of 20 mL / h via a peristaltic pump. The experiment was then cooled to 5°C at 0.1°C / min; • Keep the system at 5°C overnight. After about 9 hours at 5°C, the second step of MtBE addition was started. 190 mL was added at a rate of 20 mL / hour. The final solvent ratio was 15:85 v / v%. • The solids were isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solids was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0296] i. Crystallization 9

[0297] For crystallization of 9, the solution was seeded with 5 wt% ground seeds. Seeding was performed at 50 °C and a staged addition of MtBE was used. The slurry was cooled to 30 °C at a rate of 0.1 °C / min and held at that temperature for 8 hours. The slurry was then cooled to 5 °C at a rate of 0.1 °C / min. The following procedure was used: - Approximately 20 g of CHP Mode 1 and 2 blend (Mode 1 from as-obtained CS / 352 / 18, Mode 2 from Crystallization 8) was weighed and transferred to a jacketed vessel that had been preheated to 50°C. • Add 50 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 minutes), the experiment was maintained at 50 °C and 27.5 mL of MtBE was added manually (dropwise) using a syringe; When the addition of MtBE was complete, 1 g of CHP Mode 2 ground with a pestle and mortar was used for seeding experiments; Monitor the system at 50°C for approximately 10 minutes; 70 mL of MtBE was added at a rate of 15 mL / h via a peristaltic pump. The experiment was then cooled to 30°C at 0.1°C / min; The system was kept at 30°C for 8 hours. After 8 hours at 30°C, the system was recooled to 5°C at a rate of 0.1°C / min. In the second step, MtBE was added. 190 mL was added at a rate of 20 mL / hour. The final solvent ratio was 15:85 v / v%. • Keep the system at 5°C overnight. - After about 10 hours at 5°C, the solids were isolated by vacuum filtration using a Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 40 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. The purity of the dried solids was analyzed by XRPD, TG / DTA, PLM and HPLC; The concentration of the mother liquor after filtration was measured by HPLC.

[0298] j. Crystallization 10

[0299] Crystallization 10 used the same procedure as Crystallization 6, with the parameters scaled down to 70% of the original experiment due to the vessel size. A new batch of obtained CHP (Mode 1) (CS / 802 / 18) was also used in this experiment. The solution was seeded with 2 wt % ground seeds. Seeding was performed at 50° C. and a staged addition of MtBE was used. The slurry was cooled to 29° C. at a rate of 0.1° C. / min and maintained at this temperature for 8 hours. The slurry was then cooled to 5° C. at a rate of 0.25° C. / min. The following flow was used: About 14 g of the obtained CHP model 1 was weighed and transferred into a jacketed container preheated to 50°C. • Add 35 mL of ethanol:water (90:10 v / v%) solvent mixture to the vessel to achieve a starting concentration of 400 mg / mL. The experiment was stirred at 50°C and about 300 rpm using an overhead stirrer. • Insert the FBRM probe into the vessel to monitor and record nucleation and particle counts. When complete dissolution was achieved (approximately 20 minutes), the experiment was maintained at 50 °C and 17.5 mL of MtBE was added dropwise using a syringe; After the addition of MtBE was complete, 280 mg of CHP Mode 2 ground with a pestle and mortar was used for seeding experiments; Monitor the system at 50°C for approximately 10 minutes; • Seed crystals did not persist. An additional 3.5 mL of MtBE was added dropwise to the vessel using a syringe. Add 50 mL of MtBE at a rate of 20 mL / h via a peristaltic pump; The experiment was then cooled to 29°C at 0.1°C / min. The system was kept at 29°C for 8 hours. After 8 hours at 29°C, the system was cooled to 5°C at a rate of 0.25°C / min. Once the system reaches 5°C, start the second step of MtBE addition. Add 134 mL at a rate of 20 mL / hour. The final solvent ratio is 15:85 v / v%. • Keep the system at 5°C for about 12 hours. • The solids were then isolated by vacuum filtration using an 88 mm Buchner funnel and Whatman Grade 1 filter paper (diameter = 70 mm; pore size = 11 μm). - The filter cake was washed with 28 mL of ethanol:water:MtBE (9 vol:1 vol:30 vol) and then dried under vacuum at 40 °C for 1 hour. • The purity of the dried solid was analyzed by XRPD, TG / DTA, PLM, chiral HPLC and HPLC. • The concentration of the filtered mother liquor was determined by HPLC. Example 4 - Purity Determination

[0300] The purity of CHP and CHP-hydrate was determined using HPLC. The chromatographic parameters of the HPLC method used for purity measurement of CHP and CHP-hydrate are summarized in Table 17B. Table 17B: Chromatographic parameters of the HPLC method for CHP and CHP-hydrate purity measurement

[0301] Prepare standard solution for analytical determination (0.8 mg / mL anhydrous CHP or 0.85 mg / mL CHP hydrate): weigh approximately 40 mg of C16081735-D reference standard and transfer to a 50 mL volumetric flask. Dilute to volume with diluent and mix thoroughly (ultrasound to dissolve if necessary). Label it as STD-1 and prepare a second standard solution for standard testing. Label it as STD-2.

[0302] Prepare the sample solution (0.85 mg / mL CHP hydrate) for determination: weigh approximately 42.5 mg of CHP hydrate sample in a 50 mL volumetric flask. Dilute to a certain volume with diluent and mix thoroughly.

[0303] Representative blank chromatograms and representative resolution solution chromatograms are shown in Fig.52 and 53 middle. Example 5 - Comparison of Stability of CHP Hydrates A. Comparison of chemical stability between CHP anhydrate and CHP hydrate model 2

[0304] CHP anhydrate (mode 1) and hydrate (mode 2) compounds were prepared under GMP conditions. Stability studies of CHP anhydrate compounds were conducted for six months under accelerated conditions (40 ± 5°C / 75 ± 5% RH) and for 12 months under room temperature conditions (25 ± 5°C / 60 ± 5% RH). The stability of CHP hydrate compounds was further studied under accelerated conditions (40 ± 5°C / 75 ± 5% RH) for 6 months (Table 18). Table 18. Stability study of CHP anhydrate and mode 2 hydrate 1 T = Tested 2 NS = No schedule 3 S = Already scheduled

[0305] Long term storage conditions of CHP anhydrate require careful handling because CHP is hygroscopic. During the stability study, CHP anhydrate absorbed moisture and an increase in new impurities and a decrease in CHP anhydrate were observed due to degradation of CHP (Table 19). The stability data for CHP hydrate pattern 2 are shown in Table 20. Table 19. Impurities grown under accelerated conditions in CHP anhydrate (Mode 1) Table 20. Impurities grown under accelerated conditions in CHP hydrate (Mode 2)

[0306] CHP anhydrate absorbs water until the moisture content in CHP reaches 7%. Therefore, CHP anhydrate has a tendency to absorb water. Degradation of CHP anhydrate has also been observed. In contrast, the stable mode 2 hydrate form did not have significant mass changes during the 6-month stability study under accelerated conditions.

[0307] A comparison of total impurities between CHP anhydrate and CHP hydrate (Mode 2) is shown in Fig.54 middle. Example 6 - Polymorph Screening on CHP Hydrate

[0308] A polymorphic study of CHP was conducted with the goal of identifying any new polymorphs with improved solid-state properties. In this study, CHP pattern 2 was identified as a stable form for development, which is a stoichiometric monohydrate. The study required an initial analysis of the obtained anhydrous CHP (pattern 1, batch: 1058707), solvent solubility screening in 30 solvent systems, and primary polymorph screening using 24 solvent systems and four process-related conditions (circulation, cooling, anti-solvent addition and evaporation). Subsequently, a second screening amplification of CHP pattern 2 was performed, including a 1-week stability evaluation and pH solubility evaluation.

[0309] XRPD found the resulting material to be crystalline and composed of birefringent particles with no defined morphology. Thermally, Mode 1 was found to show three small mass losses at the onset of heating before melting of the sample was observed at 170°C, and DVS analysis indicated that a morphological change had occurred and suggested that the material produced after DVS was a hydrated form of the feed. This was supported by TG / DTA of the solid post-DVS, where the TG / DTA thermogram matched the thermal data for Mode 2 material analyzed during the second polymorph screening.

[0310] High solubility was observed in ethanol and methanol, with an estimated approximate solubility of 100 ≥ x ≥ 50 mg / mL. Using the information collected from the solubility screen, a primary polymorph screen was performed using primarily amorphous input material prepared from the resulting CHP (Pattern 1). In addition to Patterns 1 and 2, a new polymorph, pure Pattern 1, was observed in the preliminary screen.

[0311] Based on the results from the primary polymorph screening, Mode 2 was enlarged for further analysis. Thermally, the Mode 2 material was found to lose 0.9 equivalents of water from the TG / DTA experiment before recrystallization occurred at about 120°C. It subsequently melted at 170°C. The melting temperature was found to be the same as that of Mode 1, indicating that the sample dehydrated and recrystallized into Mode 1 upon heating. Although the recrystallization phenomenon was not visible in the DSC trace, evidence of recrystallization from Mode 2 to Mode 1 was evident by observation with a Hattage PLM microscope. A short-term 1-week stability study of Mode 2 CHP indicated good chemical stability under the conditions evaluated, but XRPD analysis indicated that after storage at 80°C for 7 days in a sealed vial, the Mode 2 input material converted to Mode 1. Samples stored at ambient temperature and 40°C / 75%RH remained as Mode 2.

[0312] Long-term 8-week stability studies of Mode 2 CHP demonstrated good physical stability at 40°C / 75%RH. XRPD analysis confirmed that Mode 2 was dominant throughout the duration of the 8-week evaluation.

[0313] Pure Mode 1 was initially observed during VT / VH-XRPD characterization of Mode 2, with the diffraction pattern produced at 80°C / 0%RH showing a similar peak distribution pattern to the Mode 1 material, with some missing peaks, most notably at 17° in 2θ. Further comparison with the initial Mode 2 diffraction pattern showed the presence of missing peaks in the Mode 2 diffraction pattern. This suggests that the resulting material (designated Mode 1) is a mixture of pure Mode 1 and Mode 2. Scale-up of pure Mode 1 was not successful by heating to 50°C or 80°C, but was achieved by rapid evaporation in ethanol / dichloromethane, as the ethanol / DCM mixture dissolved the material in addition to the azeotropic water, thereby promoting the formation of anhydrous Mode 1.

[0314] An eight (8) week stability study of pure Mode 1 CHP indicated poor physical stability at 40°C / 75%RH. XRPD analysis confirmed that pure Mode 1 transitioned to Mode 2 after 14 days.

[0315] Both Mode 1 and Mode 2 materials remained chirally pure throughout the duration of the stability evaluation. Despite continued work on the original sample, the material tested for stability from the 2 week time point onwards was Mode 2 rather than Mode 1 due to the poor stability of pure Mode 1 at this temperature and humidity.

[0316] Short-term 1-day stability testing of pure Mode 1 CHP showed that the material converted to Mode 2 after 2 hours at 40°C / 75% RH.

[0317] Based on the observations described in this paper, Mode 2 is emphasized as the most stable form, and a crystallization development workflow is recommended to provide a reliable and scalable process for the preparation of Mode 2 materials. A. Materials

[0318] Analyze the following materials. Batch / Lot / Sample ID: Ring (-His-Pro) Batch: 1058707 SFS ID: CS / 298 / 18 / 1 and CS / 298 / 18 / 2 Amount Received: 10g Appearance: Off-white solid

[0319] B. Analytical Methods 1. X-ray powder diffraction (XRPD)

[0320] XRPD analysis was performed on a PALAYLIC X'PERT pro, scanning the samples between 3 and 35° 2θ. The material was lightly ground to loosen any agglomerates and loaded onto a porous plate with a Kapton or Mylar polymer membrane to support the sample. The porous plate was then placed in the diffractometer and a Cu K radiation source (α1 The analysis was performed in transmission mode (with a step size 2θ of 0.0130°) using a 40 kV / 40 mA generator setup. 2. Polarized Light Microscopy (PLM)

[0321] The presence of crystallinity (birefringence) was determined using an Olympus BX50 polarizing microscope equipped with a Motic camera and image capture software (Motic Image Plus 2.0). Unless otherwise stated, all images were recorded using a 20x objective. 3. Hot stage optical microscope

[0322] Thermal phenomena were visually monitored using a calibrated Linkam THM600 heat stage with a connected controller unit coupled to an Olympus BX50 polarizing microscope equipped with a Motic camera and image capture software (MoticImage Plus 2.0). Approximately 0.5 mg of material was placed on a microscope cover glass and heated at a rate of 10°C / min, with images taken at regular intervals to record any thermal transitions. Unless otherwise stated, all images were recorded using a 10x objective. 4. Thermogravimetric analysis (TGA)

[0323] About 5 mg of material was weighed into an open aluminum pan and loaded into a coupled thermogravimetric / differential thermal analyzer (TG / DTA) and kept at room temperature. The sample was then heated from 20°C to 300°C at a rate of 10°C / min, during which the change in sample weight and any differential thermal phenomena (DTA) were recorded. Nitrogen was used as a purge gas with a flow rate of 300 cm 3 / min. 5. Differential Scanning Calorimetry (DSC)

[0324] About 5 mg of material was weighed into an aluminum DSC pan and sealed non-hermetically with a perforated aluminum lid. The sample pan was then loaded into a cooled Seiko DSC6200 (equipped with a chiller) and maintained at 20°C. Once a stable heat flow response was obtained, the sample and reference sample were heated to 250°C at a scan rate of 10°C / min and the resulting heat flow response was monitored. Nitrogen was used as a purge gas with a flow rate of 50 cm 3 / min. 6. Infrared spectrometer (IR)

[0325] Infrared spectroscopy was performed on a Bruker ALPHA P spectrometer. Sufficient material was placed on the center of the plate of the spectrometer and the spectra were acquired using the following parameters: Resolution: 4cm -1 Background scan time: 16 scan samples Scan time: 16 scans Data collection: 4000-400cm -1 Result spectrum: transmittance Software: OPUS version 6 7. Nuclear Magnetic Resonance (NMR)

[0326] NMR was performed at 500.12 MHz (for protons) using a Bruker AVIIIHD spectrometer equipped with a DCH cryoprobe. Experiments were performed in deuterated DMSO and each sample was prepared at a concentration of approximately 10 mM. 8. Dynamic Vapor Sorption (DVS)

[0327] About 10-20 mg of sample is placed in a mesh vapor sorption balance chassis and loaded into a DVS intrinsic dynamic vapor sorption balance through a surface measurement system. The sample is subjected to a ramping profile humidity increase from 40% to 90% relative humidity (RH) in increments of 10%, and the sample is kept at each step until a stable weight is obtained at 25°C (dm / dt 0.004%, minimum step length 30 minutes, maximum step length 500 minutes). After the adsorption cycle is completed, the sample is dried to 0% RH using the same procedure, and then the secondary adsorption cycle is returned to 40% RH. Two cycles are performed. The weight change during the adsorption / desorption cycle is plotted to consider the hygroscopicity of the sample. Any retained solid is then subjected to XRPD analysis. 9. Variable Temperature Dynamic Vapor Sorption (VT-DVS)

[0328] Approximately 10-20 mg of sample is placed in a mesh vapor sorption balance pan and loaded into a DVS Advantage dynamic vapor sorption balance via a surface measurement system. The sample is subjected to a ramping profile humidity increase from 40% to 90% relative humidity (RH) in increments of 10%, with the sample held at each step until the weight stabilizes at 40°C (dm / dt 0.004%, minimum step length 30 minutes, maximum step length 500 minutes). The sample is dried to 0% RH using the same procedure after the adsorption cycle is complete, and then returned to 40% RH for the second adsorption cycle. The weight change during the adsorption / desorption cycle is plotted to consider the hygroscopicity of the sample. The experiment is repeated at 50°C, and any residual solid is finally subjected to XRPD analysis at 60°C. 10. Variable Temperature and Humidity X-ray Powder Diffraction (VT- / VH-XRPD)

[0329] VT- / VH-XRPD analysis was performed on a Philips X'Pert Pro Multipurpose diffractometer equipped with a temperature and humidity chamber. The Cu K radiation source (α1 The sample was scanned between 4 and 35.99° 2θ in Bragg-Brentano geometry (step size 2θ of 0.008°) using a 40 kV / 40 mA generator setup (α1:α2 ratio = 0.5). The following measurements were made for each step of the moisture profile: Program: 40% RH / ambient temperature - initial scan 0% RH / ambient temperature - initial scan, 1 hour hold, scan 0% RH / 80℃-initial scan, 20 min hold, scan 0% RH / 80℃-initial scan, 80 minutes hold, scan 11. High performance liquid chromatography-ultraviolet detection (HPLC-UV) Instrument: Dionex Ultimate 3000 Chromatographic column: LC / 168X-X-Bridge Phenyl column (150mm×4.6mm×3.5μm) Column temperature: 30℃ Autosampler temperature: 5°C UV wavelength: 220nm Injection volume: 5 μL Flow rate: 1mL / min Mobile phase A: 10 mM ammonium acetate Mobile phase B: acetonitrile Diluent: 0.1% TFA in water Gradient Program: Time (minutes) Solvent B[%] 0.01 0 10.3 30 15 95 15.1 0 25 0 12. Liquid chromatography-mass spectrometry (LC-MS) Instrument: Dionex Ultimate 3000 Chromatographic column: ACE Excel 3 Super C18, 75×4.6mm Column temperature: 30°C Injection volume: 10 μL Flow rate: 1.0mL / min Mobile phase A: 0.1% formic acid in deionized water Mobile phase B: 0.1% formic acid in acetonitrile Diluent: Acetonitrile Needle wash: acetonitrile, vial position #100 PDA range: 190-400nm Gradient Program: Time (minutes) Solvent B[%] 0.00 5 12.00 95 15.00 95 15.10 5 20.00 5 13. Chiral HPLC Column: Daicel IC (5.0um, 250*4.6mm) Column temperature: 30°C Injection volume: 5 μL Flow rate: 1.0mL / min Mobile phase A: 0.01% DEA in n-hexane Mobile phase B: EtOH: MeOH = 2:8 (v / v) Diluent: Acetonitrile PDA range: 220nm Gradient Program: Time (min) A% B% 0.01 70 30 28.0 70 30 C. Experiment 1. Initial Characterization

[0330] Upon receipt of the provided ring (His-Pro), referred to herein as CHP, an initial characterization was performed using XRPD, PLM, TG / DTA, DSC, DVS (with post-XRPD analysis), 1H and HSQC NMR, HPLC (for purity and UV spectroscopy), pKa, and LC-MS using the techniques and methods outlined in Section B. 2. Sample Preparation for Solvent Solubility Screening

[0331] Freeze-dried in water

[0332] The material for solvent solubility screening was prepared by freeze drying as follows: · To the obtained CHP (pattern 1) (330 mg) was added 3.3 mL of distilled water to obtain a clear colorless solution; · The solution was divided equally between 33.2 mL glass vials (each vial contained approximately 100 μL and 10 mg of solid); Freeze the vials at -50°C in preparation for freeze drying; • Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 18 hours. Thereafter, samples were taken and analyzed by XRPD to confirm the amorphous nature of the batch. Repeated freeze drying in water Repeated freeze drying was performed as follows: • Redissolve 10 mg of each sample (prepared according to Section 5.2.1) in 200 μL of distilled water. Freeze the vials at -50°C in preparation for freeze drying; • Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 72 hours. Thereafter, samples were taken and analyzed by XRPD to confirm the amorphous nature of the batch. 3.Solvent solubility screening

[0333] To a known mass of CHP lyophile (10 mg, from Section 5.2.2), 100 μL of appropriate solvent was added, and if solids remained, the vial was gently heated to ~40°C to help dissolve. Continue to add solvent until the material is completely dissolved or 2 mL (<5 mg / mL) has been added. The sample was uncapped and allowed to evaporate at ambient temperature. The solvents used in the solubility screen can be found in Table 21. 4. Sample Preparation for Primary Polymorph Screening a. Freeze drying in water

[0334] The material for primary polymorph screening was prepared by freeze drying as follows: · Add 13 mL of distilled water to the obtained CHP (1.04) to obtain a clear colorless solution; • Divide the solution equally between 26 2 mL glass vials (each vial contains approximately 500 μL and 40 mg of solid); Freeze the vials at -50°C in preparation for freeze drying; • Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 48 hours. Thereafter, samples were taken and analyzed by XRPD to confirm the amorphous nature of the batch. b. Repeated freeze drying in water

[0335] The second lyophilization attempt was performed as follows: To each 40 mg sample (prepared according to part a) add 1.5 mL of distilled water to re-dissolve the material; Freeze the vials at -50°C in preparation for freeze drying; • Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 72 hours. Thereafter, samples were taken and analyzed by XRPD to confirm the amorphous nature of the batch. Table 21 Solvent solubility screening solvent list C. Repeated freeze drying in water (2)

[0336] The third lyophilization attempt was performed as follows: To every 40 mg of sample (prepared according to part b) add 1 mL of distilled water to re-dissolve the material; The solution was then pipetted into 26 20 mL glass vials and topped up with an additional 15 mL of distilled water; The vials were frozen at -50 °C in preparation for freeze drying; • Once frozen, the samples were placed in a desiccator connected to a freeze dryer and dried for approximately 120 hours. Thereafter, samples were taken and analyzed by XRPD to confirm the amorphous nature of the batch. 5. Primary polymorph screening

[0337] The primary polymorph screening of CHP was performed as follows: 24 vials from part b containing approximately 40 mg of CHP were used in this experiment; The material was suspended in an appropriate solvent / solvent mixture and the temperature was cycled between ambient temperature and 40°C for 72 hours every 4 hours. The solvents used can be found in Table 22; The resulting solid was isolated by centrifugal filtration and analyzed by XRPD. Any new forms were analyzed by TG / DTA; The filtered saturated solution was then divided into three vials for subsequent polymorph screening experiments as follows: a. evaporation

[0338] The saturated solution of CHP was transferred to 2 mL vials; these vials were then uncapped and allowed to evaporate at ambient temperature to recover the material. All recovered material was characterized by XRPD. b. rapid cooling

[0339] The saturated CHP solution was stored at 2-8°C for 96 hours. At this time, any recovered material was analyzed by XRPD and the vials were moved and stored at -20°C for 72 hours. Thereafter, any recovered material was analyzed by XRPD. c. Add antisolvent under ambient conditions

[0340] Up to 2 mL of antisolvent (heptane or MtBE) was added dropwise to the saturated solution of CHP. The sample was capped at ambient temperature for 72 hours. Any resulting solids were analyzed by XRPD. Table 22 Primary polymorph screening solvent list 6. Secondary polymorph screening a. Mode 2 Amplification

[0341] CHP Mode 2 is amplified using the method outlined below: 5 g of the obtained CHP (mode 1) was slurried in 6 mL of a 90:10 ethanol / water mixture; The resulting slurry was placed on a stirrer and stirred for about 24 hours; After 24 hours, remove the sample from the shaker and analyze the solid by XRPD; Characterize solids according to section 2.4 of P-SFS1482-00 a. Amplification of pure mode 1 i.80℃ heating mode 2 Place approximately 2.2 g of Mode 2 material (prepared according to Section 5.6.1) in a vacuum oven set at 50 °C; After 1 hour, take a sample and analyze it by XRPD; Place the vial back into the vacuum oven and raise the temperature to 60°C; After 30 minutes, samples were taken and analyzed by XRPD; Place the vial back into the vacuum oven and raise the temperature to 80°C; After 18 hours at 80°C, samples were taken and analyzed by XRPD; ii. Rapid rotary evaporation in ethanol / DCM 1 g of the obtained CHP mode 1 was weighed into a round bottom flask and dissolved in 40 mL of ethanol; Once the solid has dissolved, add 2 mL of dichloromethane to the flask using a pipette; The flask was then connected to a rotary evaporator and rapidly evaporated under vacuum at ambient temperature; - A light beige solid was recovered and analyzed by XRPD. 7. pH Solubility Evaluation

[0342] CHP models 1 and 2 were prepared for pH solubility evaluation as follows: Weigh 100 mg of each of CHP Mode 1 and Mode 2 into a 4.5 mL screw-top glass vial; Add 100 μL of the selected buffer pre-warmed to 37°C to each vial; After each volume of buffer is added, the samples are heated to 37°C in an incubator shaker for approximately 10 minutes and then checked for dissolution. C. Results 1. Initial Characterization

[0343] The initial characterization of CHP (CS / 298 / 18) is as follows: The material was crystalline as determined by XRPD ( Figure 1 ). The XRPD pattern of CHP provided is represented as Mode 1. PLM analysis found that the material is birefringent and has no clear morphology. Polarized and non-polarized images can be seen separately. Fig.12 and 11 . TG analysis shows a series of small mass losses (0.6%, 0.2% and 0.3%) from the start of heating until sample degradation is observed at approximately 280°C. DTA identifies a sharp endotherm with an onset at 170°C and a peak at 172°C, which is likely sample melting. TG / DTA thermograms are shown in Fig.14 . · Fig.16 The first thermal cycle of the DSC analysis is shown. A small broad endotherm is observed at 75°C with a peak at 85°C. A second endotherm is observed at 169°C with a peak at 171°C. This is consistent with the melting observed in the TG / DT. No significant thermal events are observed during the cooling cycle ( Fig.17 During the second heating cycle ( Fig.18 ) A very small endothermic event was observed at 75°C-80°C, most likely a weak glass transition. · Fig.23The DVS isotherm plot in shows a mass change of +6.3% from 60% RH to 90% RH, indicating a clear morphological change. After the form change, the material exhibits slight hygroscopicity with a maximum absorption of 0.8 wt% between 0 and 90% RH ( Fig.24 ). DVS kinetic diagram is shown in Fig.25 XRPD analysis confirmed that the Mode 1 feed recrystallized to Mode 2 (initially seen in the solvent solubility screen, detailed in Section 3) upon exposure to DVS humidity conditions. The XRPD diffraction pattern can be seen at Fig.26 Comparison of the Mode 1 and Mode 2 diffraction patterns showed that multiple Mode 2 peaks were also present in the resulting Mode 1, indicating that the resulting Mode 1 was a potential mixture. The Mode 2 material was further investigated by performing VT / VH-XRPD (according to Section B.1). TG / DTA analysis of the solid recovered after mode 2DVS was performed, and the thermal analysis diagram can be seen in Fig. 27 TG analysis showed an initial weight loss of 6.8% (0.95 equivalents of water) followed by sample degradation at 280°C. The DT trace identified an endotherm associated with the initial weight loss. A second endotherm was then observed at 168°C (sample melting) followed by an exotherm, most likely recrystallization of the material. · Obtained CHP 1 H-NMR( Fig.35 ) and HSQC-NMR( Fig.38 ) is consistent with the proposed structure. No imidazole CH signal was observed, probably due to slow relaxation The obtained substance was analyzed and the pKa value was found to be 6.38 ( Fig.10 ). The LC-MS spectrum of CHP mode 1 confirmed the expected mass-to-charge ratio m / z 235.1, corresponding to [C 11 H 14 N 4 O 2 ]H + ( Fig.55 ). When analyzed by HPLC-UV, the purity of CHP was 99.5%. Fig.56 2. Sample Preparation for Solvent Solubility Screening a. Freeze drying in water

[0344] Analysis of the solid obtained by freeze drying in water showed that the material was still crystalline. The 2θ diffraction pattern of the amorphous material is shown in Fig.40 . b. Repeated freeze drying in water

[0345] Analysis of replicate freeze-dried solids from water indicated that this material predominated. 3.Solvent solubility screening

[0346] As mentioned above, the solubility of CHP lyophilized product was evaluated in 30 kinds of solvents / solvent mixtures selected. As can be seen from the results of Table 23, this material demonstrates low solubility in most of the solvents / solvent mixtures used in this research. High solubility was observed in ethanol and methanol, and its approximate solubility was estimated to be 100 ≥ x ≥ 50 mg / mL. It was also observed that this material is soluble in water, DMSO, DMA, trifluoroethanol and methanol / water mixture.

[0347] Solvent solubility results from XRPD analysis of the recovered solids are shown in Table 24. Product XRPD diffractograms for each pattern produced can be found at Fig.57 The rest of the diffraction patterns are included in Figure 58-Figure 60 middle. Table 23: CHP lyophilizate solvent solubility results Table 24: Summary of XRPD patterns from solvent solubility screening 4. Sample Preparation for Primary Polymorph Screening a. Freeze drying in water

[0348] Analysis of the freeze-dried solid in water indicated that the sample was still crystalline. The diffraction pattern was determined to be Mode 2 ( Fig.61 ). b. Repeated freeze drying in water

[0349] Fig.62 The diffraction pattern obtained from repeated freeze-drying of CHP in water is shown. XRPD analysis confirmed that the crystallinity of the material was less than Fig.61 The previous sample shown in , but still contains the Mode 2 peak. c. Repeated freeze drying in water (2)

[0350] Fig.63 The diffraction pattern obtained from the third freeze-drying attempt of CHP in water is shown. XRPD analysis confirmed that the crystallinity of the material was less than Fig.61 The samples shown, however Fig.62 The peak of mode 2 still exists. 5. Primary polymorph screening

[0351] As described above, the tendency of CHP to exhibit polymorphism was evaluated in 24 selected solvents / solvent mixtures. a. Temperature Cycle

[0352] The results from the temperature cycling experiments for the primary polymorph screening are shown in Table 25. The relevant diffraction patterns are shown in Figure 64-66 . • CHP pure mode 1 was recovered from 50:50 methanol / MtBE, 10:90 methanol / MtBE, ethanol / MtBE mixtures and ethyl acetate, although some preference was apparent in this sample. • Recovery mode 1 from ethyl formate, acetonitrile, MEK and THF. • 5 solvent systems generated Mode 2; heptane, isopropyl acetate, MIBK, MtBE and toluene. • The preference in the solid produced from DCM means that no mode can be assigned. There was solid in chlorobenzene, but the yield was insufficient to perform XRPD analysis. Produces an oil in methanol. • The remaining solvent system resulted in a solution and therefore could not be analyzed by XRPD. Table 25: Primary Polymorph Temperature Cycling Screening b. Evaporation

[0353] The results of the evaporation experiments obtained from the primary polymorph screening are shown in Tables 26 and Fig.113 The relevant diffraction pattern is shown in Fig.67 . • Mode 1 for recovery of poor crystals from acetonitrile. • Mode 2 is produced twice, once from trifluoroethanol and also from nitromethane. • Amorphous material was identified from DCM and THF. • Solids were observed from 10:90 ethanol / MtBE, 50:50 ethanol / MtBE, MIBK, and ethanol, but were not produced in sufficient quantities for XRPD analysis. • Most solvent systems produced a colorless film on the vial walls that could not be analyzed by XRPD. Table 26. Primary Polymorph Evaporation Screening c. Rapid cooling

[0354] Table 27 shows the results obtained from the primary polymorph screens with quench at 2-8°C and -20°C. • Quench experiments were not performed in 50:50 methanol / MtBE and methanol due to insufficient mother liquor generated by temperature cycling. • The remaining experiments produced only solutions and therefore could not be subjected to XRPD analysis. Table 27: Quench for Primary Polymorph Screening d. Anti-solvent addition

[0355] Table 28 shows the results obtained from the primary polymorph screening with the addition of antisolvent. Fig.68 middle. Insufficient solids produced in acetone, DCM, and 50:50 ethanol / MtBE • Mode 1 (from ethanol) was the only mode observed in the antisolvent addition experiments. • Antisolvent experiments with 50:50 methanol / MtBE and methanol were not performed due to insufficient mother liquor generated by temperature cycling. Table 28. Antisolvent Addition for Primary Polymorph Screening 6. Summary of primary polymorph screening

[0356] Table 29 and Fig.114 A summary of the primary polymorph screening results is provided. Table 29: Summary of primary polymorph screening

[0357] This primary polymorph screen identified 1 new form of CHP, designated pure Pattern 1, and produced after temperature cycling. Patterns 1 and 2 were also reproduced in multiple solvent systems from temperature cycling. Snap cooling experiments from 2-8°C and -20°C returned only clear solutions. In antisolvent addition experiments, most solvent systems returned clear solutions, but Pattern 1 was seen from ethanol after the addition of MtBE. 7. Secondary polymorph screening a. Mode 2 Amplification

[0358] Fig.69 Shown is an enlarged XRPD result of Mode 2. The XRPD diffraction pattern confirmed the formation of Mode 2. b. Amplification of Mode 1 i.80℃ heating mode 2

[0359] Pure mode 1 was not successfully produced in this experiment. A mixture of mode 1 and mode 2 was recovered at 50°C and 80°C. A previously unseen peak at 8° 2θ appeared after the sample was held at 50°C for 90 minutes. After 18 hours at 80°C, the intensity of this peak increased. The relevant diffraction patterns can be seen at Fig.70 middle. ii. Rapid rotary evaporation in ethanol / DCM

[0360] Analysis of the solid recovered from the ethanol / DCM flash evaporation indicated that the material was pure Pattern 1 by XRPD. The diffraction pattern was Fig.71 middle. c. Characterization of Mode 2

[0361] Analysis of CHP Mode 2 from 90:10 ethanol / water gave the following results: The material was crystallized by XRPD and matched the crystallographic Mode 2 diffraction pattern obtained in the primary polymorph screening ( Fig.72 ). PLM images of CHP mode 2 were also taken and the material was found to be birefringent with a fragmented, rod-like morphology. Images in polarized and unpolarized light can be found at Fig.73 . Hot stage microscopy was also applied on CHP mode 2. Initial images confirmed the rod-like morphology ( Fig.74 ). This is consistent with Fig.69 The material was observed to begin melting at 95°C and to be completely melted at 101°C. Recrystallization was observed to occur at 115°C. PLM images taken after the hot stage showed that the material morphology was no longer clearly defined, but the sample was still birefringent. Polarized and non-polarized images of the material after the hot stage can be found in Fig.75 Seen in. TG / DTA-TG analysis showed an initial weight loss of 6.5%, followed by sample degradation at 280°C (0.9 equivalents of water). The DT trace identified an endotherm associated with the initial weight loss. A second endotherm was subsequently observed at 170°C (sample melting) ( Fig.76 ) is preceded by an exothermic phenomenon, most likely the recrystallization of the material. The initial thermal cycle of DSC identified an endothermic phenomenon, which started at 99°C and peaked at 102°C ( Fig.77 This is consistent with the endothermic data observed in TGA, although the recrystallization observed in TGA is not present in DSC. No heat was observed during the cooling cycle ( Fig.78 The second heating cycle determined the possible glass transition at 75 °C ( Fig.79 ). · Fig.80 The FT-IR spectrum of CHP mode 2 is shown. The peak table can be found in Table 30. VT- / VH-XRPD analysis: When the humidity was reduced to 0% at ambient temperature, the Mode 2 feed was maintained. When the temperature was increased to 80°C, the material changed to a form assigned to pure Mode 1. When kept at 80°C for 80 minutes, pure Mode 1 was maintained. Table 31 shows the humidity, temperature and mode identification at each step. The relevant diffraction patterns can be found in Fig.81 . DVS analysis of CHP mode 2 showed that the material did not change form from 40% RH to 90% RH or from 90% RH to 10% RH, but lost 3.5 wt% (0.5 equivalents of water) below 10% RH. Rehydration was observed from 0 to 90% RH. This can be seen in Fig.82 The DVS isotherm diagram can be seen. Fig.83 DVS kinetics are shown. XRPD analysis after DVS showed no change in form at 40% RH. Comparative XRPD diffractograms can be seen at Fig.84 The non-stoichiometric water loss observed in this experiment is thought to be due to the ambient temperature (about 25°C), where the kinetics of dehydration are too slow and the instrument thus moves to the next stage before completion. To investigate this further, variable temperature DVS experiments were performed as detailed below. VT-DVS analysis at 40°C showed that below 10% RH the material began to dehydrate, losing approximately 5.8 wt% from 10% to 0% RH (0.8 equivalents of water). The material subsequently rehydrated from 0 to 40% RH. DVS isotherm plots can be found at Fig.85 As can be seen in the figure, the kinetic line diagram can be found in Fig.86 DVS analysis at 50°C showed that the material began to dehydrate below 20% RH, losing approximately 6.1 wt% (0.8 equivalents of water). The material then rehydrated from 0 to 40% RH. Fig.87 Display the 50℃ isotherm diagram, Fig.88 The kinetic plot is shown. The VT-DVS at 60°C shows that the material begins to dehydrate below 20% RH, losing approximately 7 wt% or 1.0 equivalent of water. Note that the material rehydrates between 0 and 40% RH. The 60°C isotherm plot can be found at Fig.89 As can be seen in the figure, the kinetic line diagram can be found in Fig.90 XRPD analysis of the recovered solid showed that after DVS, the material was a mixture of Mode 1 and Mode 2, as can be seen in the comparative XRPD diffraction patterns. Fig.91 . - The HPLC purity of CHP pattern 2 was found to be 99.5%. Table 30: FT-IR Peak Table for CHP Mode 2 from Ethanol / Water Table 31. VT / VH-XRPD results of CHP pattern 2 8. pH Solubility Evaluation

[0362] The pH solubility evaluation for CHP mode 1 and mode 2 found that after adding 3 volumes of buffer, dissolution occurred at all tested pH values ​​(pH 1, 4, 6.8 and 7.2). The solubility of mode 1 and mode 2 was estimated to be 500≥x≥333.3 mg / mL. A summary of the results is shown in Table 32. Images of dissolved samples can be found in Fig.92 The sum of the materials in mode 1 is seen in Fig.93 See Mode 2 in the example above. Table 32. Summary of pH solubility results 9. Stability study a.1-week stability evaluation

[0363] The XRPD 2θ diffraction pattern of the sample tested at 40°C / 75% RH, 80°C and ambient light is shown in Fig.94 No morphological changes were observed for samples stored at 40°C / 75% RH or under ambient light. Based on previous thermal experiments, DVS and VT / VH XRPD experiments, it was found that Mode 2 material transformed to Mode 1 after 7 days at 80°C.

[0364] The HPLC purity results for CHP Mode 2 are listed in Table 33. Under all conditions, there was no decrease in purity after 7 days of storage. The HPLC chromatogram of the stability sample is shown in Table 33. Figures 95-97 middle. Table 33. Stability purity results of CHP mode for 21 weeks b.8-week stability evaluation i. Two-week time point

[0365] The XRPD 2θ diffraction pattern at two weeks is shown in Fig.98 is the sum of pure mode 1 Fig.99 The results show that pure mode 1 transforms into mode 2 after 14 days at 40°C / 75% RH. No morphological change was observed for CHP mode 2 after 14 days. ii. Four-week time point

[0366] The XRPD 2θ diffraction pattern at the four-week time point is shown in Fig.100 is the sum of pure mode 1 Fig.101The results show that pure Mode 1 material, which had previously transformed to Mode 2 after two weeks, remained in Mode 2 after 4 weeks at 40°C / 75% RH. No morphological changes were observed for CHP Mode 2 after 4 weeks. iii. Eight-week time point

[0367] The XRPD 2θ diffraction pattern at the eight-week time point is shown in Fig.102 is the sum of pure mode 1 Fig.103 The results show that after two weeks, pure Mode 1 material that had previously transformed to Mode 2 remained in Mode 2 after 8 weeks at 40°C / 75% RH. No change in the form of CHP Mode 2 was observed after 8 weeks. iv. Appearance test

[0368] Table 34 and Fig.115 The appearance test results of the 8-week stability study are shown. The appearance of pure Pattern 1 and Pattern 2 remained consistent throughout the experiment. Table 34: Summary of 8-week stability appearance results v. Chiral HPLC

[0369] HPLC analysis confirmed that both pure Mode 1 and Mode 2 input samples had high chiral purity. There was no change in chiral purity over the entire duration of the stability evaluation. A summary of the results can be found in Table 35. HPLC chromatograms are shown in Figure 104-Figure 110 . Table 35: Summary of chiral HPLC results c. 1-day stability evaluation

[0370] The XRPD results stored at 40°C / 75%RH are shown in Fig.111 After 2 hours at 40°C / 75%RH, pure Mode 1 was found to transform into Mode 2. Initial experiments also included additional time points at 4, 6 and 8 hours, but the experiment was stopped after 2 hours when the material transformed into Mode 2 after the first time point. d. Summary of results 1. Initial Characterization

[0371] The material CHP provided was found to be crystalline by XRPD and birefringent by PLM with no well-defined morphology. The material had several mass losses of 0.6, 0.2 and 0.3% of TG / DTA and was found to degrade when heated to 280°C. Melting was also observed at 170°C. DSC gave results of a small endothermic phenomenon at 75°C, which was attributed to the loss of solvent (water). A second endothermic phenomenon was observed at 169°C, with a peak at 171°C. This is consistent with the melting observed in TG / DT. No obvious thermal phenomenon was observed in the cooling cycle, but a weak glass transition was observed at 75°C during the second heating cycle.

[0372] DVS data showed a +6.3% mass change from 60% RH to 90% RH, indicating a significant recrystallization phenomenon. After recrystallization, the material exhibited slight hygroscopicity, with a maximum absorption of 0.8 wt % between 0% and 90% RH. XRPD analysis after DVS confirmed the change in form. The diffraction pattern produced after DVS was designated as Mode 2 and determined to be a hydrated form of Mode 1. TG / DTA after DVS showed that the Mode 2 input material dehydrated and lost 6.8 wt % (0.95 equivalents of water) when heated. Recrystallization was subsequently performed before melting the sample at 168°C. The temperature of the melt was consistent with that of the Mode 1 melt. The melting point consistency between the two samples means that before recrystallization into Mode 1, Mode 2 was a monohydrate and lost about 1 equivalent of water when heated.

[0373] NMR data were consistent with the proposed structure and showed no solvent content. 2. Solvent solubility

[0374] The CHP (pattern 1) obtained shows low solubility in most of the solvents / solvent mixtures used in this study. High solubility was observed in methanol and ethanol, and its approximate solubility was estimated to be 100≥x≥50mg / mL. It was also observed that the material was soluble in water, DMSO, DMA, trifluoroethanol and methanol / water mixture. Pattern 2 was the only new crystal form (except the pattern 1 obtained) determined during this experiment. Pattern 2 was reclaimed from 17 kinds of solvent systems, and pattern 1 was only seen from 1-propanol. The mixture of pattern 1 and pattern 2 was seen from ethanol. THF reclaims the amorphous material with some pattern 2 peaks. 3. Primary polymorph screening

[0375] This primary polymorph screen identified 1 new form of CHP, designated pure Pattern 1, and produced after temperature cycling. Patterns 1 and 2 were also reproduced in multiple solvent systems from temperature cycling. Rapid cooling experiments at 2-8°C and -20°C recovered only clear solutions. In anti-solvent addition experiments, most solvent systems returned clear solutions, but Pattern 1 was seen from ethanol after the addition of MtBE. 4. Secondary polymorph screening

[0376] Secondary polymorph screening found that CHP mode 2 was successfully scaled up from ethanol / water. Analysis of the material yielded the following results: - The material crystallized by XRPD and matched the crystallinity of the Mode 2 diffraction pattern obtained in the primary polymorph screen. • PLM images of CHP mode 2 were also taken and the material was found to be birefringent with a fragmented, rod-like morphology. Initial images taken at the beginning of the hot-stage microscopy experiment identified a rod-like morphology consistent with the PLM images of Mode 2. The material was observed to begin melting at 95°C and to be completely melted at 101°C. Recrystallization was observed to occur at 115°C. PLM images taken after the hot stage indicated that the material morphology was no longer clearly defined, but the sample was still birefringent. TG / DTA-TG analysis showed an initial weight loss of 6.5% followed by sample degradation at 280°C. The DT trace identified an endotherm associated with the initial weight loss. An exotherm was then observed at 170°C before a second endotherm (sample melting), most likely recrystallization of the material. The initial thermal cycle of DSC identified an endotherm with an onset at 99° C. and a peak at 102° C. This is consistent with the endotherm data observed in TGA, although the recrystallization observed in TGA was not present in DSC. No thermal events were observed during the cooling cycle, but a small glass transition was observed at 75 °C during the second heating cycle. VT- / VH-XRPD analysis: When the humidity was reduced to 0% at ambient temperature, Mode 2 was retained into the material. When the temperature was increased to 80°C, the material changed to a form designated as pure Mode 1. When kept at 80°C for 80 minutes, pure Mode 1 was retained. DVS analysis of CHP Mode 2 showed that the material did not change form from 40% RH to 90% RH or from 90% RH to 10% RH, but lost 3.5 wt% (0.5 equivalents of water) below 10% RH. Rehydration was observed from 0 to 90% RH. XRPD analysis after DVS showed no change in form at 40% RH. VT-DVS - The sample dehydrated to less than 10% RH at 40°C and less than 20% RH at 50 and 60°C. The material lost a higher percentage of water at each temperature increase, but rehydrated from 0 to 40% RH in each experiment. After VT-DVS, a mixture of patterns 1 and 2 can be seen by XRPD. - The HPLC purity of CHP pattern 2 was found to be 99.5%.

[0377] Without success in reproducing pure Mode 1 upon heating to 80°C, a mixture of Modes 1 and 2 was confirmed by XRPD. XRPD also identified a previously unseen peak at 8° 2θ once the sample was held at 50°C for 90 minutes. After 18 hours at 80°C, the intensity of this peak increased. This peak was not seen in any other diffraction pattern produced in this study.

[0378] Pure Pattern 1 was successfully re-prepared by rapid evaporation in ethanol / DCM. 5.1-week stability study

[0379] The 1-week stability study showed that Pattern 2 exhibited good chemical stability under the conditions evaluated (40°C / 75% RH, 80°C and ambient light). After 7 days, no change in purity was observed for any of the samples.

[0380] The elevated temperature of 80°C resulted in dehydration from Mode 2 to Mode 1 after 1 week, but the material did remain in Mode 2 when stored at 40°C / 75% RH and ambient light. 6.8-week stability study

[0381] The 8-week stability study showed that the pure Mode 1 material exhibited poor physical stability at 40°C / 75% RH, with the material transitioning to hydrated Mode 2 after the first (two-week) time point. Although studies continued on the original sample, the material tested for stability from the 2-week time point onwards was Mode 2 rather than Mode 1 due to the poor stability of pure Mode 1 at this temperature and humidity. No changes in appearance were observed at any of the time points tested, although XRPD confirmed changes in form.

[0382] In contrast, Mode 2 showed good physical stability with no changes in form observed over the duration of the 8-week stability evaluation. The appearance of the Mode 2 material did not change at any point throughout the experiment. Both pure Modes 1 and 2 were found to have high chiral purity at the start of the 8-week evaluation and maintained high chiral purity in all samples throughout the duration of the experiment. 7.1-Day Stability Study

[0383] The 1-day stability assessment confirmed that pure Mode 1 material readily transformed to Mode 2 under high humidity conditions. XRPD analysis confirmed that the morphology change occurred after only 2 hours at 40°C / 75% RH. 8. pH Solubility Evaluation

[0384] pH solubility evaluation for both CHP Mode 1 and Mode 2 found that dissolution occurred at all pH values ​​tested (pH 1, 4, 6.8, and 7.2) after the addition of 3 volumes of buffer. The solubility for Mode 1 and Mode 2 was estimated to be 500≥x≥333.3 mg / mL. e. Conclusion

[0385] Long-term 8-week stability studies of Pattern 2 CHP showed good physical stability at 40°C / 75% RH. XRPD analysis confirmed that Pattern 2 was dominant throughout the duration of the 8-week evaluation. Eight (8) week stability studies of pure Pattern 1 CHP showed poor physical stability at 40°C / 75% RH. Pattern 2 is the form of CHP most suitable for further development.

[0386] Example 7 - Stability Study

[0387] Purpose: To obtain stability data for drug substances during storage and manufacture under GMP conditions.

[0388] Packaging: At each individual time point, the samples were packed in double antistatic LDPE bags, all secured with cable ties. The samples packed under the same storage conditions were stored together in a fiber drum, closed with a metal lid. All packages were prepared and labeled in the same way. Details on the description of the packaging materials are provided in Table 36. Table 36. Packaging material description Note: Antistatic LDPE bags were provided by STA and were cut into small pieces and heat-sealed before use in stability studies.

[0389] Time zero is the date the sample is placed on the station. Initial test results are from release testing as long as the sample is placed on the station within 30 days of the release test date, otherwise the initial test is repeated. The stability protocol is provided in Table 37. Table 37. Stability scheme Test Item X = Extract samples and test appearance, content and impurities by HPLC, chirality and water content Y = Extract sample and test XRPD “---”=Not scheduled

[0390] Study requirements: Total sample volume 22.5 g (if not required for initial testing, total sample volume 21 g): · If required, initial test 1.5 g; Divide the 21g sample into 14 portions, 1.5g each, and weigh each portion into a double antistatic LDPE bag fixed with a cable tie. Store the stability samples of each storage condition together in a fiber drum, close it with a metal lid, and then store them at 25±2℃ / 60+5% RH (9 bags) and 40±2℃ / 75±5% RH respectively. (5 bags). Sampling time:

[0391] Pull samples that have been stored for no more than 6 months on or within 2 working days after the scheduled date. Pull samples that have been stored for more than 6 months on the scheduled date + 2 working days. Sample storage and testing cycle limitations:

[0392] Stability samples stored for one month to one year and greater than one year should be analyzed and completed within 10 and 20 working days, respectively, after removal from the stability chamber. If a time zero test is performed, it should be analyzed within 10 working days of the start of the study.

[0393] Detailed information on the stability of Mode 2 is provided in Table 38 and Table 39. Table 38. 6 month stability results at 25°C / 60% RH. *Note: Reference standard (lot number: PS03027-15-H) was used for XRPD analysis. Reference standard (lot number: 1056491) was used for other chemicals. * 1 Note: The initial date refers to the release COA of C180726100-H. Table 39. 6 month stability results at 40°C / 75% RH.

[0394] The results of the stability samples met the acceptance criteria of this specification. Representative overlay chromatograms of blank, resolving solution and sample solution (6M) for impurity testing are provided in Fig.112 middle.

[0395] The embodiments described herein are intended to be exemplary. Those skilled in the art will appreciate that changes and modifications may be made without departing from the scope of the invention as encompassed by the appended claims.

Claims

1. Use of a cyclic (-His-Pro) hydrate in the preparation of a medicament for treating acute kidney injury, chronic kidney disease or renal fibrosis, characterized in that: The X-ray powder diffraction (XRPD) diffraction pattern of the hydrate includes peaks at 2θ of 10±0.2°, 13.7±0.2°, 17±0.2°, 18.1±0.2° and 27.3±0.2°; the initial endotherm of differential scanning calorimetry (DSC) is 75°C to 100°C; the initial exotherm of DSC is 115°C to 120°C; the DSC thermogram has two endothermic peaks with maximum peaks at 100°C and 170°C; the chemical structure of cyclo(-His-Pro) hydrate is 2. The use according to claim 1, wherein: Further comprising at least two of the following features: (a) an X-ray powder diffraction pattern, further comprising a peak at 2θ of 20.2±0.2°; (b) birefringence with a fragmented, rod-like morphology when analyzed by polarized light microscopy; (c) When analyzed by thermogravimetric analysis technique, the initial weight loss was 6.5%, and then the sample degraded at 280 °C; (d) In the first thermal cycle of DSC, the endotherm starts at 99 °C and peaks at 102 °C; (e) dehydration begins at less than 10% relative humidity (RH), loss of 6 wt% from 10% to 0% RH and hydration from 0% to 40% RH in a 40° C. dynamic vapor sorption analysis; and (f) In the 60°C dynamic vapor sorption analysis, dehydration started below 20% RH, 7 wt% was lost from 20% RH to 0% RH, and rehydrated from 0% RH to 40% RH.

3. The use according to claim 1, wherein: The hydrate has a purity of at least 90%.

4. The use according to claim 1, wherein: The hydrate has a purity of at least 95%.

5. The use according to claim 1, wherein: The hydrate has a purity of at least 96%.

6. The use according to claim 1, wherein: The hydrate has a purity of at least 97%.

7. The use according to claim 1, wherein: The hydrate has a purity of at least 98%.

8. The use according to claim 1, wherein: The hydrate has a purity of at least 99%.

9. The use according to claim 1, wherein: The hydrate has a purity of 100%.

10. The use according to claim 1, wherein: The hydrate is stable at room temperature for 6 months, 12 months, 18 months, 24 months or 36 months.